Theoretical modeling and experimental validation of flexural behavior for corrugated steel plate and mold-bag concrete composite tunnel support - Pengfei li; Ruiwei Hu; Yongli Tao; Zhengdong Huang; Yuhan Shan (Tunnelling and Underground Space Technology, 2026)

Single-cell transcriptomic profiling identifies TIMP1 as a diagnostic marker linked to macrophage ferroptosis in ulcerative colitis - Wen-Hao Xiong; Shuo Huang; Yan-Hong Liu; Guo-Shan Chen; Dan-Zhou Li; Yong-Cheng Di; Wen-Bin Song; Yong-Chao Zhang; Yi-Fan Wang; Feng Qi (Tissue and Cell, 2026)

Late Neoarchean garnet-biotite gneiss widely distributed in the Wulashan area, northwestern North China Craton: Implications for the late Neoarchean tectonic environment and the origin of ca. 2.45 Ga metamorphic zircons - Daomao Huang; Hangqiang Xie; Shuguang Li; Pengchuan Li; Shoujie Liu; Shan Ke; Chunyan Dong; Yusheng Wan (Lithos, 2026)

Efficient tandem hydrodeoxygenation of vanillin over NiCo@C/KCe-10: Benefits of promotion by carbon coating and Ce doping - Pengpeng Huang; Shouteng Zheng; Xincheng Li; Yunfei Zhi; Kai Yuan; Mingming Fan; Pingbo Zhang; Tengfei Niu; Yan Leng; Yane Zheng; Lihong Jiang; Shaoyun Shan (Fuel, 2026)

Gum arabic crosslinked by 4-(4,6-dimethoxy-1,3,5-triazin-2-yl)-4-methylmorpholinium chloride: Interfacial behavior and emulsification enhancement - Yongpeng Yin; Jianing Cai; Yingzhi He; Kun Huang; Xiner Ning; Shan Sun; Dingding Li; Beiwei Zhu; Xiaoming Guo (Food Hydrocolloids, 2026)

The critical x[I/L]xbS motif in adaptor proteins, MAVS, MITA, and TRIF contributes to type I IFN production and antiviral immune response in fish - Xue Yun Peng; Jing Hou; Bo Li; Chuan Yun Zhang; Lin Huang; Lan Hao Liu; Nan Li; Pin Nie; Shan Nan Chen (Fish & Shellfish Immunology, 2026)

Dietary protein digests regulate the intestinal absorption of lipopolysaccharide by reshaping its physicochemical states and release kinetics during gastrointestinal digestion - Zixin Huang; Mengzhen Ding; Yafang Ma; Di Zhao; Kai Shan; Weixin Ke; Guanghong Zhou; Chunbao Li (Food Research International, 2026)

HiMA-seq enables cost-effective spatiotemporal transcriptomics with high sensitivity and flexible multiplexity - Jiahe Liu; Zhidong Tang; Shan Jiang; Peiqing Miao; Shimei Yin; Ziwei Zhou; Li Lei; Dong Cheng; Xiru Liu; Liuyang Zhao; Ailong Huang (Chemical Engineering Journal, 2026)

Spatial distribution and compositional profile of microplastics in oil and gas extraction solid wastes: An overlooked source of microplastics - Yongxu Jin; Jianqi Dai; Xiang Wang; Shan Zhong; Yingzhou Huang; Xudong Mei; Shijie Wang; Min Hao; Jinwei Fang; Yunmin Zeng; Dong Li (Chemical Engineering Journal, 2026)

Aging and photodegradation of polycyclic aromatic compounds (PACs) emitted from biomass burning under sunlight and ultraviolet radiation - Ya-Jing Li; Zhen-Shan Huang; Yu-Ping Chen; Zhi-Hui Su; Yi-Huan Chen; Yuan Zeng; Yu-Qi Huang; Yu-Feng Guan; She-Jun Chen (Atmospheric Environment, 2026)

Effects of dietary yeast cell wall supplementation on growth performance, serum enzyme activity, and immune gene expression in Pacific white shrimp (Litopenaeus vannamei) - Chuan Chen; Xinhe Ruan; Jinhong Shan; Zijie Xuan; Huitao Cheng; Fengqi Huang; Lihua Li; Zongyang Li; Xiaoling Zuo; Jie Yu; Huihong Zhao (Animal Feed Science and Technology, 2026)

Under greenhouse settings, mycorrhizal responsive herbs establish better in their own soil compared to less responsive counterparts - Stavros D. Veresoglou; Yang Liu; Jie Bai; Hanzhi Bao; Peipei Bao; Bolun Cai; Liqun Cai; Jiawei Cao; Chen Chen; Genrun Chen; Hongqiao Chen; Jiarong Chen; et al. (Plant and Soil, 2026)

The impact mechanism of coupling tailwater reuse with tillage layer construction on nutrient substitution and pollution control in paddy fields - Jian Zhang; Qinglin Li; Renjie Hou; Zhaoqiang Zhou; Anshuang Su; Miao Wang; Hai Xu; Wei Huang; Shan Zhao (Soil and Tillage Research, 2026)

Fipronil and its metabolites in a tropical estuary: multi-compartment distribution, trophic transfer, and risk assessment - Yu-Han Xie; Can Huo; Zhi-Yan Wang; Shan-Shan Yao; Heng-Xiang Li; Yu Zhong; Xiao-Ping Huang; Xiang-Rong Xu (Marine Environmental Research, 2026)

Enhanced phytoextraction of manganese and cadmium by Polygonum lapathifolium L. via Enterobacter sp. inoculation: Roles of rhizosphere regulation and endophytic microbiome assembly - Yi Li; Chijian Tang; Yinghao Mo; Yong Shan; Ziang He; Yaoheng Huang; Cuiping Wan; Rifeng Wu; Chunlai Zhang; Jiang Liang; Tongbin Zhu; Fangming Yu (Journal of Hazardous Materials, 2026)

Neurotoxicological Concerns: Azole Fungicides as Mixed/Noncompetitive Inhibitors of Human and Rat 5α-Reductase 1 - Jiachen Lin; Yinghao Huang; Yilin Xu; Zhiqiang Yu; Chentao Ding; Mengru Li; Yingfen Ying; Ren-shan Ge; Yiluan Wang (Journal of Hazardous Materials, 2026)

Submicron-scale mineral weathering and organo-mineral association in the rhizosphere of iron ore tailings - Zhen Li; Songlin Wu; Ting-Shan Chan; Cheng-Wei Kao; Jian Wang; Gordon Southam; Longbin Huang (Geochimica et Cosmochimica Acta, 2026)

pH and polyphenol-controlled release dual-responsive intelligent hydrogel absorbent pad strategy: methylcellulose‑sodium alginate and anthocyanin@MOFs for chilled pork preservation - Yanpei Huang; Conghui Lang; Fei Ren; Jinsheng Fu; Shengmin Liu; Chuang Zhang; Kai Shan; Chunbao Li; Wenxue Chen; Ming Zhang; Qiujin Zhu; Haiming Chen (Food Research International, 2026)

Screening of immune adjuvants for an attenuated live vaccine derived from the Aeromonas veronii TH0426 strain with a hisJ gene deletion and evaluation of its immune protection in crucian carp - Qixing Huang; Ruitong Li; Shuoyu Wang; Ruiqi Liang; Peiqi Lu; Bingmei Du; Yan Cheng; Xiaochen Ren; Jinhong Li; Xu Dong; Jiaojiao Yang; Luyao Chu; et al. (Fish & Shellfish Immunology, 2026)

Leucobacter faecis sp. nov., a Novel Actinomycete Isolated from Bat Feces of Rousettus and Hipposideros spp. - Yuyuan Huang; Jing Yang; Qinglian Qin; Zedan Yang; Xiaoting Wei; Ziwei Lin; Wenbo Luo; Wudi Wei; Zongxiang Yuan; Li Ye; Junjun Jiang; Shan Lu; et al. (Current Microbiology, 2026)

Microbial drivers of ecosystem recovery in the Qinghai-Tibetan Plateau's alpine mining soils: Alpha diversity, network complexity, and keystone taxa - Jiang He; Mingyang Zhang; Xiaoxiao Liang; Yu Huang; Jiexia Li; Shan Luo; Zijian Xu; Zhixiang Sun; Longxin Guo; Zhenhua Zhang; Shuping Zhang; Yongkun Zhang; et al. (Agriculture, Ecosystems & Environment, 2026)

Intracranial EEG reveals working memory-related dynamics and connectivity in human white matter - Shen Zhang; Peng-Hu Wei; Longzhou Xu; Chao Zhang; Na Ao; Haoshu Xu; Yanfeng Yang; Lirou Tan; Zhilin Li; Yali Huang; Jin Li; Jing Liu; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Advantages of double-sided different curvature corrugated shells in stability: hydrostatic pressure tests and deformation failure mechanisms - Cunyao Shan; Jianliang Sun; Jiashuai Yang; Yuchen Li; Qiaogao Huang; Bin Wang; Xu Zhang (Ocean Engineering, 2026)

MFN2-mediated remodelling of ER-mitochondria communication alleviates ochratoxin A-induced hepatocyte ferroptosis by enhancing mitophagy - Zi-Yan Hu; Rui-Qi Liu; Yu-Xuan Ouyang; Ming-Shan Chen; Jia-Xin Wang; Ming Lou; Yi-Feng Huang; Hong-Li Si; Fu-Wei Jiang; Zhuo-Yu Liu; Yi-Bo Wang; Li Wang; et al. (Journal of Hazardous Materials, 2026)

Electron-networking Cu single atom-spurred Ru clusters for anion exchange membrane water electrolysis - Zihao Zhou; Rui Qin; Tingjie Mao; Pinlin Wang; Zhongliang Huang; Ting-shan Chan; Yu-cheng Huang; Zhiwei Hu; Xiaoqing Huang; Nanjun Chen; Yunhua Li (Chemical Engineering Journal, 2026)

Differences between human and rat 5α-Reductase 1 inhibition by phenolic disinfectants: Comparative kinetics and binding modes for neurosteroid synthesis - Xinyu Han; Wanyu Li; Yinghao Huang; Lisha Wang; Tianchi Zhao; Xishi Chen; Hao Lin; Yiyan Wang; Ren-shan Ge; Jianfeng Ma (Chemico-Biological Interactions, 2026)

Research advances in machine learning-aided accurate prediction of the impact of exogenous substances on anaerobic digestion - Chuqiao Wang; Zijing Wang; Runjie Deng; Shan Huang; Yuying Hu; Dingchang Li; Xiaoming Peng; Xizi Long; Jiajie Zhang (Bioresource Technology, 2026)

PM2.5 and ozone in the yangtze river economic belt, 2013–2023: Dynamics and drivers, with scenario-based PM2.5 projections and health implications to 2050 - Yiwei Chen; Haixing Zhao; Sen Li; Guangmao Zhang; Zhouyi Du; Ting Huang; Shan Huang; Xiang Tu; Zugen Liu; Honggen Peng (Atmospheric Pollution Research, 2026)

Quantifying the light interception and canopy photosynthesis of strip intercropping system based on 3D canopy photosynthesis model - Si-Rong Huang; Qing-Feng Song; Zheng Guo; Qiu-Feng Long; Li-Sha Zhang; Yue Li; Yuan Yang; Xiao-Chun Wang; Feng Yang; Tai-Wen Yong; Jiang Liu; Yan-Hong Yan; et al. (Computers and Electronics in Agriculture, 2026)

Unraveling antibiotic fate in a highly urbanized estuary: Spatiotemporal patterns, multi-media partitioning, and contaminant prioritization - Nian-Nian Wu; Shan Liu; Ru Xu; Qian-Yi Huang; Yun-Feng Pan; Heng-Xiang Li; Lang Lin; Rui Hou; Xiang-Rong Xu; Xiao-Ping Huang (Marine Pollution Bulletin, 2026)

A single-cell transcriptomic atlas of the spotted scat testis reveals two Sertoli cell subclusters with differential dmrt1Y expression - Yu Li; Mou-Yan Jiang; Shan-Ni Cao; You-Xing Peng; Yuan-Qing Huang; Hong-Juan Shi; Hua-Pu Chen; Tian-Li Wu; Dong-Neng Jiang (Aquaculture, 2026)

SlERF.F4 negatively regulates tomato fruit susceptibility to Botrytis cinerea independently of ripening traits - Yu Zhao; Pan Wu; Yulin Huang; Sumin Guo; Xiaofen Yu; Donald Grierson; Lei Gao; Shan Li (Postharvest Biology and Technology, 2026)

Microplastics distinctly regulate cadmium accumulation and lipid homeostasis in maize: Mechanistic insights from membrane remodeling to gene expression - Huijun Li; Xiaodie Zheng; Honghong Shan; Yichao Huang; Chuanxin Ma; Jian Zhao; Xiaochen Huang (Journal of Hazardous Materials, 2026)

Environmental controls on soil nematode composition and network complexity across a restoration chronosequence in a mining-affected alpine grassland on the Qinghai–Tibet Plateau - Jiang He; Mingyang Zhang; Yu Huang; Jiexia Li; Shan Luo; Zhixiang Sun; Longxin Guo; Zhenhua Zhang; Shuping Zhang; Huakun Zhou; Yongsheng Yang (Journal of Environmental Management, 2026)

Observations of polycyclic aromatic hydrocarbons at Changbai Mountain in Northeast Asia: Characteristics, transboundary transport, and health impacts - Ye Shan; Yifan Li; Lanxin Zhang; An’an Qi; Yujiao Zhu; Yanbin Qi; Lingxiao Yang; Liubin Huang; Jiangshan Mu; Mingxuan Liu; Hongyong Li; Lingli Zhang; et al. (Journal of Environmental Sciences, 2026)

Association of volatile organic compounds with serum lactate dehydrogenase levels in the general adults - Ruitong Liao; Xiaoping Huang; Yue Xu; Qingya Zhao; Xiaogang Lv; Qi Liu; Qianqian Ji; Liuqing Li; Minghe Xu; Weiqing Chen; Yunzhang Wang; Shan Xu; et al. (International Archives of Occupational and Environmental Health, 2026)
Objectives This study aimed to investigate the associations between urinary metabolites of Volatile organic compounds (mVOCs) and serum Lactate dehydrogenase (LDH) levels in a representative sample of the U.S. adults. Methods We analyzed data from 4907 participants in NHANES 2011–2018. Seventeen urinary mVOCs were measured, and serum LDH was used as the outcome. Generalized linear models (GLM), restricted cubic splines (RCS), and weighted quantile sum (WQS) regression were used to assess linear, nonlinear, and mixture effects. Sensitivity analyses were conducted using urinary creatinine-corrected mVOC concentrations, and quantile g-computation (qgcomp) was applied as an alternative mixture modeling approach to validate the robustness of our findings. Furthermore, false discovery rate (FDR) correction was applied to account for multiple comparisons. Results Several mVOCs were significantly associated with serum LDH. Notably, 2MHA, 34MHA, ATCA, and CYMA showed robust inverse associations, while PHEM was positively associated with LDH. RCS models revealed non-linear exposure–response relationships for multiple mVOCs. WQS regression indicated that both positively and negatively weighted mVOCs contributed to LDH levels, with DHBMA as a major positive contributor and 34MHA as a negative contributor. Most associations remained stable after sensitivity analyses. Conclusions This study demonstrates that urinary mVOCs are associated with serum LDH levels, suggesting potential subclinical toxic effects of VOC exposure. These findings underscore the need for environmental risk management and further investigation into the biological pathways linking VOCs to systemic health outcomes.

Endothelial cell-specific knockout of ATG5 ameliorates inflammation and renal fibrosis by regulating pyroptosis - Yu Huang; Shu Wen; Li Chen; Yujiu Gao; Shufan Xu; Chen Fang; Jian Tang; Yue Yuan; Ying Feng; Shinan Ma; Shan Luo; Qinghong Zhang; et al. (Inflammation Research, 2026)

Substituting Chemical Fertilizer with Chicken Manure Alters Soil Dissolved Organic Matter and Volatile Organic Compound Profiles in Chinese Cabbage - Yuwei Zhang; Shan Tang; Qi Jin; Wei Gao; Ya-Li Li; Shao-Wen Huang; Hong Wang (Journal of Soil Science and Plant Nutrition, 2026)

Antibiotic transport and release effects in paddy soil-water system under water level regulation modes - Jian Zhang; Qinglin Li; Renjie Hou; Zhaoqiang Zhou; Qiang Fu; Tianxiao Li; Anshuang Su; Hai Xu; Miao Wang; Wei Huang; Shan Zhao (Water Research, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

First fossil fruit of Spatholobus (Papilionoideae, Fabaceae) from East Asia - Yi-Shan Zhao; Zhen-Dong Cao; Jing-Nan Huang; Zi-Yi Li; Torsten Wappler; Zhen-Xian Zhang; Shu-mei Xiao; Wei-Yu-Dong Deng; San-Ping Xie (Review of Palaeobotany and Palynology, 2026)

Source-to-sink processes of an estuary in an ocean-current-dominated strait: Jiulongjiang Estuary, Taiwan Strait - Tao Lan; Yalong Li; Xin Shan; Yuting Huang; Xuefa Shi (Marine Geology, 2026)

Long-term exposure to sandstorms-related particulate matter and risks of all-cause and cause-specific mortality in a national cohort study - Hailu Zhu; Xinran Shan; Xingyao Tang; Linhong Pang; Zhaoyang Pan; Zijun Li; Yicong Wang; Qi Wang; Ke Huang; Tianjia Guan; Ting Yang; Chen Wang (Journal of Hazardous Materials, 2026)

FeS2/NC composite with Fe−Nx and Fe−Cx reactive sites to efficiently activate peroxymonosulfate for the degradation of carbamazepine under visible light - Shan Huang; Jiangxue Luo; Tianren Zhan; Yubo Wu; Jiankun Li; Yanjuan Zhang; Zuqiang Huang; Huayu Hu; Tao Gan (Journal of Environmental Chemical Engineering, 2026)

Valorization of phosphogypsum and municipal sludge into functional ceramic filter for closing the loop in the phosphorus chemical industry: A sustainable "waste-treats-waste" strategy - Shuaicheng Huang; Zebing Zhu; Lili Shan; Zhuye Ni; Xiaoni Li; Jingliang Dong; Changlong Pang (Journal of Cleaner Production, 2026)

Hydrophobic deep eutectic solvents for highly efficient n-hexane capture - Yan Zhao; Yanlong Xu; Anna Mei; Yingzhe Chen; Chee Sien Wong; Zhao Huang; Yulong Shan; Jianmeng Chen; Qian Li; Dong-Zhi Chen (Journal of Environmental Sciences, 2026)

The physicochemical and simulated digestive characteristics of yam flours processed by different thermal processing methods - Ya Huang; Mei Deng; Xuchao Jia; Lihong Dong; Fei Huang; Qin Ma; Mingwei Zhang; Shan Liang; Yanxia Chen; Fengjuan Li; Ruifen Zhang (Food Chemistry, 2026)

An inactivated vaccine confers potent and durable protection against a screened virulent rhabdovirus in hybrid snakehead - Guo Zheng; Yujie Lin; Mingju Luo; Shan Li; Qiuming Cen; Ying Zhong; Jinlu Huang; Lining Zhao (Fish & Shellfish Immunology, 2026)

Frost heave in soils: Research status and perspectives - Jidong Teng; Jinfeng Li; Jizhong Huang; Feng Shan; Sheng Zhang; Daichao Sheng (Earth-Science Reviews, 2026)

Biochar reshapes phosphorus distribution in soil aggregates and improves rice phosphorus uptake - Jiajun Wu; Bin Zhou; Zhehao Huang; Zichuan Li; Jingyuan Pan; Kaihao Zhang; Cheng Liu; Yanjun Chai; Yan Li; Muhammad Azeem; Nicholas Clarke; Shengdao Shan (Soil Ecology Letters, 2026)

Complete genome sequence of a lytic phage, vB_KaeP_KM5, infecting multidrug-resistant Klebsiella aerogenes - Xundie Li; Xinyi Zheng; Meijia Huang; Hongjuan Zhang; Hanyu Liu; Shaoxuan Li; Xiaoyan Zhu; Bin Shan (Archives of Virology, 2026)

Uranium occurrence state in coal gangue and study on uranium leaching via chemical mechanical-thermal activation - Shan Li; Jiulong Cui; Lin Ma; Tingting Zheng; Wentao Li; Gen Huang; Jiushuai Deng; Yijun Cao; Junguo Li; Hongxiang Xu; Zechao Huangfu (Process Safety and Environmental Protection, 2026)

A LaMnO3-based porous hydrogel evaporator for synergistic solar desalination and photocatalytic purification - Shan Chen; Yuangao Li; Liyan Xue; Xiaojing Li; Heng Chen; Qinghao Zhao; Minzhong Huang; Yiqun Deng; Fan Yang (Journal of Water Process Engineering, 2026)

Analysis of different fermentation processes of jujube-hawthorn fermented beverage based on untargeted metabolomics and GC–MS - Zhibin Xing; Yueyao Li; Hao Huang; Hexi Yuan; Xiaoqiang Zhang; Xinrui Liu; Chunhui Shan; Xizhe Fu; Yinglin Du (Food Research International, 2026)

Release kinetics and environmental risks of TCPP from polyurethane foam microplastics: Insights from artificial seawater to natural estuarine water - Shan-Shan Yao; Yu-Han Xie; Zhi-Yan Wang; Shan Liu; Rui Hou; Lang Lin; Yu Zhong; Xiao-Ping Huang; Heng-Xiang Li; Xiang-Rong Xu (Environmental Pollution, 2026)

Multifunctional TP-P-Co-MOF for epoxy resins: Simultaneously achieving flame retardancy, smoke suppression, and mechanical reinforcement - Xueying Shan; Qixin Huang; Jiao Gao; Hanchao Liu; Jingru Wang; Jinchun Li (Chemical Engineering Journal, 2026)

Sustainable graphene from biomass via flash Joule heating: An innovative approach for cement mechanical performance - Xiaolian Su; Linyue Ge; Shan Huang; Xinye Wang; Hao Xie; Yiqiang Liu; Li Yi; Lingqin Liu; Junguang Meng; Haining Meng (Biomass and Bioenergy, 2026)

Light-at-night exposure drives myopia via melanopsin signalling - Jiaxin Li; Congying Li; Meijun Wang; Jianjun Meng; Jiajia Dang; Ying Huang; Di Shi; Xinyu Li; Shan Cai; Tianli Peng; Yunfei Liu; Yuting Kang; et al. (Science China Life Sciences, 2026)

Multi-omics analysis provides genetic evidence for the involvement of cell adhesion pathway in the pathogenesis of biliary atresia - Rui Dong; Jinhang Zhu; Chunjing Ye; Fenglong Sun; Cong Huai; Wei Zhou; Jiajie Zhu; Xiaoqi Feng; Qiange Xiao; Deqian Chen; Yifan Yang; Ran Yang; et al. (Science China Life Sciences, 2026)

Dual-functional NiCo2O4 nanofibers/chitosan aerogel for efficient solar evaporation and bacterial removal - Yuangao Li; Shan Chen; Rengfeng Luo; Liyan Xue; Heng Chen; Fengzhi Tan; Minzhong Huang; Zhaoli Liu; Fan Yang (Journal of Environmental Chemical Engineering, 2026)

Regenerative treatment of aquatic pollutants of microplastic and antibiotics based on synergistic effect of magnetic biochar/protonated g-C3N4 - Zifeng Li; Rui Shan; Guoqiang Wei; Leyi Huang; Dong Liang; Haoran Yuan; Yong Chen (Journal of Environmental Chemical Engineering, 2026)

Divergent driving mechanisms elevate antibiotic resistance risk to a greater extent in water than in sediment of the Ganjiang River: The synergistic effect of mobile genetic elements and microbial metabolism - Dingchang Li; Rongmei Zhu; Xiaoyan Fan; Huihui Dai; Chenglong Zou; Yanling Wang; Jinchi Yao; Huimin Zhang; Chuqiao Wang; Shan Huang (Journal of Environmental Chemical Engineering, 2026)

Leveraging deep learning and spectral information for enhanced variety identification of safflower seeds - Hao Huang; Wen-Xia Li; Chao-Chuan Jia; Hui Yan; Shan-Yong Yi; Lei-Lei Gao; Cun-Wu Chen; Bang-Xing Han; Fang Wang (Food Chemistry, 2026)

Identification method for crosswind nonlinear aerodynamic damping model parameters in tall slender structures considering non-Gaussian response induced by self-excitation - Qingshan Yang; Shuai Huang; Zhanfang Liu; Wenshan Shan; Chen Li (Engineering Structures, 2026)

Priming indigenous microbial manganese oxidation with aged biochar for cadmium immobilization in acidic soils - Yongchao Li; Yangxin Zhai; Chuanfeng Zhou; Anqi Bu; Yanming Wang; Yesheng Huang; Shengdao Shan (Chemical Engineering Journal, 2026)

Strong and tough liquid crystal hydrogels from chitin whiskers with multiscale dynamic bonds guide osteogenic differentiation - Wei Wen; Yizhi Li; Xinxin Huang; Haiyang Xia; Chunhua Chen; Shan Ding; Lu Lu; Lihua Li; Mingxian Liu; Changren Zhou; Binghong Luo (Carbohydrate Polymers, 2026)

Chemical constituents from Sargentodoxa cuneata and their chemotaxonomic significance - Lu-Shan Li; Huanlai Huang; Jia Yang; Rong-Yuan Deng; Ji-Ye Liang; Zhong-Bo Zhou (Biochemical Systematics and Ecology, 2026)

The Influence of M1 and DLPFC iTBS on BCI Performance: A TMS and fNIRS Study - Jing Chen; Ya-wen Li; Shan-tong Yao; Yu-hong Huang; Wen-ming Ma; Zhi-hong Li; Yue Lan; Guang-qing Xu; Qian Ding (Translational Stroke Research, 2026)

Impacts of long-term fertilizer reduction and organic substitution on microbe-mediated multi-nutrient in agricultural ecosystems - Zhenling Li; Jiawei Ying; Xiaokang He; Yangyang Li; Guangchun Shan; Chenghong Feng; Mingjun Ding; Gaoxiang Huang; Jia Liu (Agriculture, Ecosystems & Environment, 2026)

The transcription factor BRN2 confers cadmium tolerance by regulating SAM1 expression in Arabidopsis - Su Li; Jing Huang; Jia Qi Li; Chuan Jin Shan; Ren Fang Shen; Da Li Zeng; Jin Chen; Xian Jiao Guan; Xiao Fang Zhu; Ting Wu Liu; Yong Gang Xu (Plant Science, 2026)

Phosphate-solubilizing bacteria enhance cadmium phytoremediation by Solanum nigrum L. through improved phosphorus availability and cycling in contaminated soil - Shiyu Luo; Chijian Tang; Yong Shan; Cuiping Wan; Yinghao Mo; Yaoheng Huang; Rifeng Wu; Fangming Yu; Yi Li (Journal of Hazardous Materials, 2026)

Deciphering the dynamic interactions among ammonia emissions and composting parameters in sewage sludge composting using multi-stage machine learning - Jie Liu; Weiguang Li; Guangchun Shan; Yuxin Huang; Huanzhang Feng; Shuncai Wang; Caihua Bai (Journal of Environmental Management, 2026)

The migration and transformation behavior of gallium and germanium during coal combustion - Haoyang Gao; Shan Wang; Bo Wei; Kunpeng Liu; Hanghang Zhang; Zongfa Li; He Huang (Fuel, 2026)

Selective enrichment of nitrogen-metabolizing species in agricultural small water bodies: the potential regulation of additives from microplastics color - Qian Zhang; Xinhui Huang; Hongyu Shan; Peizhao Li; Jin Cui; Lishan Zhang; Shan Zhong; Xuan Ru; Zongchen Li; Xiaohua Shu (Bioresource Technology, 2026)

Genome-Wide Identification and Expression Analysis of the TCP Gene Family in Quinoa (Chenopodium quinoa Willd.) - Yutao Bai; Heng Zhang; Guofei Jiang; Xuqin Wang; Lingyuan Zhang; Ping Zhang; Junna Liu; Li Li; Hanxue Li; Liubin Huang; Shan Zhang; Rongbo Li; et al. (Journal of Plant Growth Regulation, 2026)

Large Potential for CH 4 Mitigation and Yield Improvement in China's Paddies Through Locally Optimized N Management - Haoyu Qian; Zhengqi Yuan; Xiangcheng Zhu; Yuanfa Huang; Min Li; Jiarui Li; Yuxin Ren; Jinfei Feng; Shan Huang; Wenjun Dong; Feng Jin; Jiping Gao; et al. (Global Change Biology, 2026)
Nitrogen (N) management is critical for ensuring food security and mitigating greenhouse gas (GHG) emissions. In rice paddies, the effectiveness of N management in maximizing yields and minimizing N losses is highly dependent on local environmental conditions and thus varies widely across regions. However, the influence of optimized, site‐specific N management on methane (CH 4 ) emissions remains poorly quantified and is not reflected in current IPCC Tier 1 methodologies. Here, we synthesize data from multiregional field experiments and conduct a meta‐analysis to show that locally optimized N management practices—such as delayed fertilizer application, reduced N input, and deep placement—reduce CH 4 emissions from rice paddies by 16%–21%. The experiments further show that these practices suppress CH 4 emissions by lowering soil N availability and organic matter decomposition, thereby limiting substrates for methanogenesis. Combining survey data from 155 counties with machine learning models, we estimate that implementing optimized N strategies across China's rice‐growing regions could reduce CH 4 emissions by 16% while simultaneously increasing rice yields by 7%. These findings underscore the dual benefits of locally optimized N management for agricultural productivity and climate change mitigation, and provide a foundation for improving CH 4 emission estimates under diverse management regimes.

Arsenic species in crayfish from the Yangtze River basin, China: Levels composition and health risk assessment - Xinjie Li; Bo Fu; Kai Lin; Jiayin Huang; Sisi Yu; Wenchao Zhu; Yuli Lin; Chiqun Shan; Mingqin Zhong; Shaoyou Lu (Aquaculture, 2026)

Balancing rice production and greenhouse gas mitigation: assessing the feasible potential of agricultural practices - Qiang Xu; Dicai Ao; Xin Li; Xiangcheng Zhu; Zihao Wang; Yi Yang; Pete Smith; Baojing Gu; Lei Liu; Jinyang Wang; Shuhao Tan; Ziyin Shang; et al. (Resources, Conservation and Recycling, 2026)

Use of Pseudomonas lurida QNF3 as a biocontrol agent to control postharvest apple ring rot - Yonghong Huang; Hanting Wang; Jinghui Li; Xiaoying Shan; Juan Liu; Liping Yan (Postharvest Biology and Technology, 2026)

Water-assisted thermal polymerization synthesis of cobalt-doped porous g-C3N4/Ni2P composites for enhanced photocatalytic hydrogen evolution - Liqin Liu; Dan Li; Tianci Huang; Jian Li; Yanli Zhuang; Xinxin Jin; Lianwei Shan; Hao Sun; Limin Dong; Jie Yao (Fuel, 2026)

Experimental and numerical investigation on seismic performance of seawater sea-sand coral aggregate concrete filled UHPC tubular columns - Chengdong Lu; Dingkuan He; Bo Shan; Peicheng Qin; Tianyu Li; Bin Huang; Xinlin Fu; Gang Liu (Engineering Structures, 2026)

Short-term and long-term effects of outdoor artificial light at night on reproductive hormones among infertile women from a preconception cohort study - Wenbin Fang; Cun Huang; Ying Tang; Mengdie Li; Yaning Sun; Yanlan Tang; Yinyin Chen; Yawen Cao; Jiqi Fang; Kunjing He; Jing Shen; Zhiyuan Huang; et al. (International Journal of Biometeorology, 2026)

Quick Prediction of Earthquake Ground Shaking Intensity Using High-Rate GNSS: A Case Study of the 2021 Mw 7.3 Maduo Earthquake - Zhiyu Gao; Yanchuan Li; Xinjian Shan; Chuanchao Huang; Xing Huang; Kai Zheng; Bo Li (Journal of Earth Science, 2026)

Multi-source assessment of permafrost deformation along the Bei'an–Hei'he highway in Northeast China - Aoxiang Yan; Shanzhen Li; Xiaoying Jin; Shuai Huang; Wenhui Wang; Jianjun Tang; Anyuan Li; Ze Zhang; Shengrong Zhang; Jinbang Zhai; Lanzhi Lü; Ruixia He; et al. (Remote Sensing of Environment, 2026)

Cinnamon essential oil alleviates postharvest loquat browning by enhancing the antioxidant system through GABA-mediated ROS metabolism - Xinhui Zhang; Shan Wang; Shuqiong Xia; Mengjie Bian; Weizhong You; Hongli Qie; Yicheng Wang; Chong Shi; Yaqiong Wu; Lianfei lyu; Zhengjin Huang; Fuliang Cao; et al. (Postharvest Biology and Technology, 2026)

Thermal resistance and stability of multilayers embedding probiotic structure - Ping-Hsiu Huang; Chien-Shan Chiu; Wen-Chien Lu; Chang-Wei Hsieh; Po-Hsien Li (Journal of Food Engineering, 2026)

Corrigendum to “Mortality risk of short-term air pollution exposure in urban and rural Chinese populations: A nationwide time-stratified case-crossover study, 2008–2020” [Int. J. Hyg Environ. Health 266 (2025) 114564] - Yunning Liu; Hongbing Xu; Xuyang Shan; Xinpeng Guan; Lijun Wang; Xinghou He; Jiangmei Liu; Jinling You; Rongshan Wu; Jianbin Wu; Bin Zhang; Jinlei Qi; et al. (International Journal of Hygiene and Environmental Health, 2026)

Dibifree, a dietary phytomix, improves glycemic control and adiposity via modulation of the gut–pancreas–adipose–immune axis in type 2 diabetes - Tzu-Yi Huang; Niann-Tzyy Dai; Hsiu-Jung Liao; Ly Hien Doan; Tai-Shan Cheng; Wen-Yu Hsieh; I-Hsuan Lin; Yu-Tang Huang; Chia-Ching Liaw; Hsiao-Sheng Liu; Wei-Ming Cheng; Chun-Li Su; et al. (Food Research International, 2026)

Novel Zn2Cys6 transcription factor AfEcm22 positively regulates aflatoxin biosynthesis in Aspergillus flavus - Shan Wei; Shan Pei; Donghai Li; Fangjing Jia; Di Chen; Yang Lei; Fengguang Zhao; Yangyong Lv; Yuansen Hu; Liang Huang (Food Bioscience, 2026)

Plant colonization facilitates organic matter humification, iron mineral transformation, and microbial community restructuring in coal gangue remediation - Junsheng Guo; Zhen Li; Yirui Shi; Tingrui Zhang; Yuanfang Huang; Jianying Shang; Ting-shan Chan; Songlin Wu; Yunjia Liu (Environmental Research, 2026)

Quantitative resolution analysis in seismic imaging: From classical theory to cutting-edge advances - Jidong Yang; Jianping Huang; Hejun Zhu; Jiaxing Sun; Li-yun Fu; George McMechan; Houzhu Zhang; Ru-Shan Wu (Earth-Science Reviews, 2026)

Sophora moorcroftiana seeds ethanol extract alleviates non-alcoholic fatty liver disease through adjusting lipid metabolism via LKB1/AMPK signalling pathway - Xiao Chen; Mingxue Cui; Xiaojing Sun; Liying Gao; Haifeng Liu; Ruiying Yuan; Sicen Wang; Shan Huang; Bin Li (Natural Product Research, 2025)

Release kinetics and bioaccessibility of heavy metal from antifouling paint particles in simulated digestive fluids: An emerging threat to marine biota - Zhen-Liang Li; Ting-Ting Xu; Shan-Shan Yao; Heng-Xiang Li; Shan Liu; Rui Hou; Lang Lin; Zhi-Xin Ni; Qun Xie; Xiao-Ping Huang; Xiang-Rong Xu (Marine Pollution Bulletin, 2025)

Bio-inspired fabrication of heterostructured porous core-shell PANI@Cu2O/CMC composite beads for green catalysis in A3 and decarboxylative A3 couplings - Shuyao Zhang; Ting Lin; Yuling Huang; Jiayi Huang; Meiling Xue; Zhihao Shan; Yiqun Li (Sustainable Chemistry and Pharmacy, 2025)

Performance of blood biomarkers in internal jugular vein for Alzheimer’s disease pathologies: the Delta Method study - Jun Wang; Dong-Yu Fan; Shan Huang; Chang Liu; Pei-Wen Zhao; Nan Wu; Xiao-Lin Gao; Qing-Zhi Wang; Yanli Li; Bai Liu; Yuan-Ye Ma; Rong-Chang Zhao; et al. (Science Bulletin, 2025)

FuHsi regulates rDNA transcription and promotes tumor progression - Xiaohui Yang; Ao Ding; Songzhe Wu; Ziyue Jiang; Yifei Li; Xianting Huang; Liqiang Duan; Shuwen Cheng; Shizhong Zheng; Shan Gao (Science Bulletin, 2025)

A review of flexible fluid-structure interactions in the ocean: Progress, challenges, and future directions - Sasan Tavakoli; Mansi Singh; Saeed Hosseinzadeh; Zhengyu Hu; Yaniln Shao; Shan Wang; Luofeng Huang; Apostolos Grammatikopoulos; Yuzhu Pearl Li; Danial Khojasteh; Jin Liu; Azam Dolatshah; et al. (Ocean Engineering, 2025)

Geochemical constraints on origin of high-silica granite and volcanic-plutonic connection: An example from Ningwu volcanic basin, Eastern China - Jiancheng Xie; Sujuan Zhou; Lin Qian; Qian Feng; Liu Yang; Shan Huang; Quanzhong Li; Jianmin Liu; Jun Yan (Lithos, 2025)

Agricultural plastic films reshape soil microplastic distribution, nitrogen cycle and ecological risks in facility agriculture - Hao Wang; Gaoxiang Huang; Xiaokang He; Guangchun Shan; Zhenling Li; Mingjun Ding; Chenghong Feng; Caixia Yan (Journal of Hazardous Materials, 2025)

DeepSANet: A deep learning approach for hierarchical geographical source attribution of Salmonella - Shan Liang; Shaohui Mei; Jiahao Ji; Bingkui Li; Mingyuan Xu; Miaomiao Chen; Yawen Huang; Yuxin Zheng; Di Chen; Xiangyu Deng; Shaoting Li; Hongmei Zhang (Food Research International, 2025)

Combining untargeted metabolomics and chemometrics to reveal the metabolic profiles of jujube-hawthorn fermented beverages at different fermentation stages - Zhibin Xing; Tarun Belwal; Hao Huang; Xiang Li; Liangxia Han; Yahui Yin; Chunhui Shan; Xizhe Fu; Yinglin Du (Food Chemistry, 2025)

Three new acidic polysaccharides from steamed Polygonatum cyrtonema Hua modulate immunomodulatory activities via TLR4-mediated MAPK and NF-κB pathways - Yanling Wang; Lanlan Wu; Yuan Zhang; Qianglai Tan; Shan Huang; Yuhuan Li; Huanxin Wang; Chaoxiang Chen; Weijing Wu (Food Bioscience, 2025)

CuO/PVA-based ultra-low-volume oral H2S detection system to reveal tongue coating effects - Moumita Deb; Chang-Chuan Huang; Yen-Ming Lai; Chang-Ju Chu; Yu-Shan Lee; Chien-Ting Chen; William Lee; Hsin-Fei Meng; Li-Yin Chen; Olivier Soppera; Chao-Sung Lai; Ding-Han Wang; et al. (Chemical Engineering Journal, 2025)

Trend in chemical components and sources of PM2.5 and its relationship with ozone in central PRD, China (2018–2023) - Jianfan Yin; Shan Huang; Yunqian Liao; Zihan Li; Bin Yuan; Ming Chang; Weiwen Wang; Xiongzhou Lv; Xihua Li; Shuzhen Su; Xuemei Wang; Min Shao (Atmospheric Environment, 2025)

Distribution characteristics and pollution evaluation of heavy metals in surface sediments in China’s largest freshwater lake - Xiaolong Zhang; Xiaofeng Li; Weiqiang Dai; Weihao Zhang; Xiangwen Zhang; Daishe Wu; Shan Huang; Ting Huang (Stochastic Environmental Research and Risk Assessment, 2025)

Silencing aquaporin 1 inhibits autophagy to exert anti-rheumatoid arthritis effects in TNF-α-induced fibroblast-like synoviocytes and adjuvant-induced arthritis rats - Man-yu Zhang; Meng-qing Wang; Yan Huang; Sheng-long Gu; Meng-yuan Zhou; Ze-shan Xu; Ling-ling Li; Min Lv; Li Cai; Rong Li (Inflammation Research, 2025)

Identification of homeobox gene family in Chenopodium quinoa and expression patterns in response to flooding stress during the filling stage - Guofei Jiang; Li Li; Yutao Bai; Xuqin Wang; Lingyuan Zhang; Ping Zhang; Junna Liu; Hanxue Li; Liubin Huang; Shan Zhang; Peng Qin (Genetic Resources and Crop Evolution, 2025)

Chlorholones A−H, bioactive sesquiterpenoids with diverse skeletons from Chloranthus holostegius - Zhao-Chun Zhan; Ting Lu; Hai-Shan Zhang; Mei-Ting Weng; Hui-hui Zhu; Qiang Lin; Hai-Yue Zhao; Yue-Hao Huang; Tian-Yuan Wu; Miao Wang; Yao-Lan Li; Yi-Wen Zhang; et al. (Phytochemistry, 2025)

Rapid and deep removal of fluorine from wastewater by porous La-Al layered double hydroxides material: Reaction mechanism coupled with chemical precipitation and adsorption - Wenxia Hu; Yuchao Tang; Kun Wang; Fazhi Xie; Changnian Wu; Weihua Li; Caihong Chen; Xianhuai Huang; Jun Wang; Chengqi Ye; Shan Li; Can Wang; et al. (Journal of Water Process Engineering, 2025)

Cardiorespiratory benefits of reducing indoor particulate matter depend on immune improvements: Insights into individual heterogeneity from a randomized, double-blind crossover trial - Aojing Han; Wenlou Zhang; Luyi Li; Di Yang; Yetong Zhao; Qisijing Liu; Wanzhou Wang; Shan Liu; Xuezhao Ji; Xiaoming Shi; Jing Huang; Shaowei Wu; et al. (Journal of Hazardous Materials, 2025)

Response of invasive Solidago canadensis to foliar application of natural herbicide and glyphosate - Muhammad Anas; Zhi-Yun Huang; HuAnHe Xiong; Muhammad Imran; Meng-Ting Yan; Qaiser Javed; Guang-Qian Ren; Shan-Shan Qi; Jian Li; Zhi-Cong Dai; Dao-Lin Du (Journal of Environmental Management, 2025)

Development of a rapid method for the determination of the spatial distribution of protein in wheat grain using mature resin section and image processing algorithm - Hengtong Wang; Haijiang Min; Minghao Gao; Han Zhong; Chuan Zhong; Zenan Ban; Qin Zhou; Xiao Wang; Jian Cai; Qing Li; Mei Huang; Dong Jiang; et al. (Journal of Cereal Science, 2025)

Establishing a robust area-to-volume scaling for Qinghai-Tibetan Plateau Retrogressive Thaw Slumps: A key tool for quantifying mass wasting and carbon release induced by permafrost degradation - Jiapei Ma; Genxu Wang; Chunlin Song; Dexin Gao; Jinlong Li; Peng Huang; Linmao Guo; Kai Li; Shan Lin; Shouqin Sun (Global and Planetary Change, 2025)

Volatile organic compounds in various workplaces and during commutes in a Chinese city: occurrence and health risks for different occupations - Jin-Long Mai; Yi Yang; Yuan Zeng; Song Liu; Zhen-Shan Huang; Jia-Hua Wu; Ya-Jing Li; She-Jun Chen (Environmental Research, 2025)

Interfacial copolymerization electrode enhanced high performance vanadium redox flow batteries - Qiuze Wang; Xueying Shan; Hanchao Liu; Lei Chen; Jianyu Cao; Yucheng Huang; Haiguang Gao; Jinchun Li (Chemical Engineering Journal, 2025)

Chitin whisker liquid crystal hydrogel embedded with polyacrylic acid templating osteoid-like Bouligand structure for guiding internal mineralization - Ruixi Zhang; Yiting Luo; Wei Zhou; Xinxin Huang; Runshan Huang; Wei Wen; Shan Ding; Hong Li; Mingxian Liu; Changren Zhou; Binghong Luo (Carbohydrate Polymers, 2025)

Recipient Periodic Fasting Promotes Osteogenesis of Implanted Mesenchymal Stromal Cell Aggregates and Safeguards Diabetic Mandibular Bone Regeneration - Zi-Qi Zhang; Yuan Yuan; Xiao-Hui Zhang; Jia-Ning Liu; Yuan Cao; Lu Liu; Lu-Fan Yang; Yi-Han Xiao; Shan-Shan Huang; Bing-Dong Sui; Jian-Fei Liang; Ji Chen; et al. (Stem Cell Reviews and Reports, 2025)

Retraction Note: Fluoxetine is Neuroprotective in Early Brain Injury via its Anti-inflammatory and Anti-apoptotic Effects in a Rat Experimental Subarachnoid Hemorrhage Model - Hui-Min Hu; Bin Li; Xiao-Dong Wang; Yun-Shan Guo; Hua Hui; Hai-Ping Zhang; Biao Wang; Da-Geng Huang; Ding-Jun Hao (Neuroscience Bulletin, 2025)

Regulation of ammonia stress adaptation in Penaeus vannamei gills: responses of endoplasmic reticulum stress and Ca2+ homeostasis - Wenheng Li; Changjian Li; Fang Wang; Zhitao Huang; Hongwei Shan (Journal of Oceanology and Limnology, 2025)

Retraction Note to: Overexpression of miR-429 impairs intestinal barrier function in diabetic mice by down-regulating occludin expression - Tao Yu; Xi-Ji Lu; Jie-Yao Li; Ti-Dong Shan; Can-Ze Huang; Hui Ouyang; Hong-Sheng Yang; Ji-Hao Xu; Wa Zhong; Zhong-Sheng Xia; Qi-Kui Chen (Cell and Tissue Research, 2025)

Mn-doped carbon dots-based fluorescent-colorimetric dual-mode probes for selective and sensitive detection of Cr(VI) ions and l-ascorbic acid via smartphone-integrated analytical platform - Shan Huang; Wenqian Zhang; Bo Li; Guixin Li; Wei Ni; Yi Fang; Fuxiang Wei; Qi Xiao (Analytica Chimica Acta, 2025)

Carbon accounting methods and carbon-reduction technologies in the tobacco industry: a comprehensive review from a full life cycle perspective - Jielin Zhu; Yi Chen; Zhumei Luo; Yonglei Jiang; Shan Qing; Chenghang Li; Zhili Xiang; Haoming Huang (Environment, Development and Sustainability, 2025)

Anthropogenic pressures amplify high-risk antibiotic resistome via co-selection among biocide resistance, virulence, and antibiotic resistance genes in the Ganjiang River basin: Drivers diverge in densely versus sparsely populated reaches - Dingchang Li; Huihui Dai; Huimin Zhang; Chuqiao Wang; Chenglong Zou; Shan Huang; Yanling Wang; Jinchi Yao (Journal of Hazardous Materials, 2025)

Longhua, the first five-element (Ni-Co-As-Ag-Bi) hydrothermal vein deposit in China: Constraints from mineral characteristics and fluid evolution - Xinshuo Huang; Mingjian Cao; Baolin Zhang; Noreen J. Evans; Zengsheng Li; Xinyu Zou; Shuo Wang; Pengfei Shan; Junyu Li; Guangming Li; Kezhang Qin (Journal of Asian Earth Sciences, 2025)

Benzotriazole (BT) and benzothiazole (BTH) derivatives as emerging marine pollutants in the Pearl River Estuary: Spatiotemporal distribution, environmental fates, and ecological risks - Xiaoxiao Chen; Qianyi Huang; Rui Hou; Shan Liu; Hengxiang Li; Tiantian Chen; Xiangrong Xu (Environmental Pollution, 2025)

Adaptive mechanisms of moss (Campylopus schmidii) to Cr(Ⅵ) stress in pyrite-mining polluted ecosystems: Integrating biochemical, structural, and molecular perspectives - Huayan Huang; Xin Zheng; Shan Tao; Shiyu Ma; Shuang Feng; Yanglong Li; Ke Liang; Guorui Li; Jia Lei; Huakang Liu; Heng Xu (Environmental Pollution, 2025)

Rapid gelation of anti-swelling polyion-complex hydrogel with self-healing property and high stretchability for underwater sensing and salvaging - Hanchao Liu; Tong Zhang; Yihao Huang; Liping Huang; Jiaojiao Fang; Boyou Hou; Xueying Shan; Jinchun Li (Chemical Engineering Journal, 2025)

Crystallization regulation and defect passivation of perovskite films via resonance-structured ionic additive for high-performance solar cells - Guogen Huang; Yuqing Dong; Guanlin Li; Zebing Gao; Chuanlin Gao; Kangbo Sun; Haoxuan Zeng; Haohua Wu; Jinxing He; Xinting Wang; Qing Bai; Tong Shan; et al. (Chemical Engineering Journal, 2025)

Emodin regulates nucleation and crystal growth of ZIF-8 for developing the size-dependent nanotherapeutics - Taotao Huo; Xiaoyu Shan; Ziyi Wang; Jiaqi Song; Liang Shao; Yuquan Bai; Xianyi Yu; Qingyuan Yang; Guanying Li; Rongqin Huang (Chemical Engineering Journal, 2025)

Urine-derived solids as nutrient sources to enhance microbial wood degradation in a composting environment - Anran Li; Xueyi Mai; Sijie Huang; Prithvi Simha; Cees J.N. Buisman; Wei-Shan Chen (Chemical Engineering Journal, 2025)

Emission of marine microbes via sea spray aerosol generation: Enrichment, influencing factors and the potential role in marine carbon cycle - Linyao Wu; Ting Liu; Yingyi Zhang; Yuhan Shen; Yinxi Yao; Zhaokang Ruan; Yee Jun Tham; Wei Song; Shan Huang; Jun Li; Senchao Lai (Atmospheric Environment, 2025)

Single-cell sequencing analysis and multiple machine learning methods identified immune-associated SERPINB1 and CPEB4 as novel biomarkers for COVID-19-induced ARDS - Hua Yang; Wenjing Wang; Junnan Huang; Yan Yan; Shan Wang; Qianran Shen; Jingjie Li; Tianbo Jin (The Science of Nature, 2025)

Genome-wide identification and expression analysis of C2H2 zinc finger protein transcription factor in quinoa - Xuqin Wang; Xingmei Zong; Guofei Jiang; Lingyuan Zhang; Yutao Bai; Ping Zhang; Junna Liu; Li Li; Hanxue Li; Liubin Huang; Shan Zhang; Peng Qin (Genetic Resources and Crop Evolution, 2025)

Identification and Analysis of Potential Biomarkers Associated with Neutrophil Extracellular Traps in Cervicitis - Wantao Liang; Yanyuan Bai; Hua Zhang; Yan Mo; Xiufang Li; Junming Huang; Yangliu Lei; Fangping Gao; Mengmeng Dong; Shan Li; Juan Liang (Biochemical Genetics, 2025)

LncRNA HAND2-AS1 Inhibited Colon Cancer Progression By Regulating miR-3118/ZG16 Axis - Ling Hu; Linfeng Xie; Shan Huang; Qiu Li (Biochemical Genetics, 2025)

Antitumor effects of Cypaliuruside F from Cyclocarya paliurus on HepG2 cells - Shan-Bin Li; Jian Zou; Tong-Shi-Yao Zhao; Bin Liang; Li-Sheng Wang; Lan-Zhen Huang; Cheng-Qin Liang; Xian-Li Zhou (Natural Product Research, 2025)

Assessment of the efficacy of Corbicula fluminea in controlling Ichthyophthirius multifiliis infections - Tian Qin; Yang-Yang Pan; Ke Huang; Wei-Shan Zhao; Ying-Zi Pan; Hong Zou; Wen-Xiang Li; Shan-Gong Wu; Gui-Tang Wang; Ming Li (Aquaculture, 2025)

Evaluation of ecological risks of antibiotics in Danjiangkou Reservoir basing on toxicity potency and antibiotic resistance genes transfer - Ruiwen Li; Yindan Zhang; Shuyin Li; Shan Chen; Chengchen Huang; Lihua Yang; Na Zheng; Yongyong Guo; Jian Han; Bingsheng Zhou; Yingcai Wang (Science of The Total Environment, 2025)

28,29-Di-nor-triterpenoid and indole diketopiperazine alkaloids from the endophytic fungus Aspergillus versicolor - Junguo Huang; Shan Ran; Guanghui Yang; Liangxiu Liao; Di Li; Qingpei Liu; Wenjing Wang; Xiaolong Yang (Phytochemistry, 2025)

Sheep and rapeseed cake manure promote antibiotic resistome in agricultural soil - Chenyu Huang; Tianyu Wang; Weibin Chen; Jiao Wang; Minrong Cui; Conglai Zheng; Mengting Qiu; Mei Shan; Baotong Li; Luqing Zhang; Yunlong Yu; Lihui Xu; et al. (Journal of Hazardous Materials, 2025)

Herbivore-induced plant volatile (Z)-3-hexenyl acetate impairs larval performance and adult fecundity of cotton bollworm - Baojuan Zeng; Mina Jiang; Shan He; Jiong Liu; Yongkang Huang; Lu Li; Guanqing Zhai; Xi Zhang; Shutang Zhou (Journal of Pest Science, 2025)

Prevalence of Avian Influenza Viruses and Biomolecular Analysis of H9N2 Subtype in Live Poultry Markets from 2021 to 2023 in Changsha, China - Xian Zhang; Yutong Wang; Xiaoyu Li; Zheng Huang; Huiyuan Fu; Ruiqing Pei; Caiying Zhu; Yu Di; Shan Chen; Jingfang Chen; Mingzhong Xu; Xuewen Yang; et al. (Food and Environmental Virology, 2025)

Selective enrichment of potential pathogens and antibiotic resistance genes derived from farmland residual microplastic films - Gaoxiang Huang; Hao Wang; Zhenling Li; Xiaokang He; Guangchun Shan; Peng Wang; Mingjun Ding; Chenghong Feng (Applied Soil Ecology, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

A series of meroterpenoids with highly oxygenated skeletons from the endophytic fungus Penicillium sp. and their anti-inflammatory activities - Tu-Xiang Mo; Liu-Xia Lv; Xi-Shan Huang; Jia-Tong Zhou; Qian Wu; Xian-Hua He; Li-Qi Liang; Wei-Feng Xu; Jun Li; Rui-Yun Yang (Phytochemistry, 2025)

Immobilization-biotrickling filter for the removal of hydrogen sulfide: Optimal conditions and biodegradation mechanisms - Xiangle Chen; Xiaojuan Huang; Xiang Wang; Shan Zhong; Tian Liang; Wenrou Yu; Quanwei Lv; Yuting Li; Xin Huang; Chuan Huang; Li’ao Wang; Sergei Sokolov (Journal of Environmental Chemical Engineering, 2025)

Decoding the role of Bacillus: Unraveling the transformation of bioactive compounds during the aging of Pericarpium Citri Reticulatae - Yanjiao Fu; Chao Wang; Zhipeng Gao; Yanfang Liao; Zixuan Li; Wenbin Xiao; Mingwang He; Yuwen Wang; Fuhua Fu; Gaoyang Li; Donglin Su; Lvhong Huang; et al. (Food Research International, 2025)

Dual associations of post-sleep and pre-wake light-at-night (LAN) exposure with myopia in children and adolescents - Di Shi; Jiaxin Li; Jiajia Dang; Yunfei Liu; Ziyue Chen; Yaqi Wang; Jieyu Liu; Xinxin Wang; Shan Cai; Yihang Zhang; Tianyu Huang; Haihua Chen; et al. (Environmental Research, 2025)

Eccentric compressive performance of H-shaped steel-reinforced geopolymer recycled aggregate concrete-filled GFRP tube columns - Dongming Huang; Dong Zhao; Zhenzhen Liu; Yiyan Lu; Shan Li (Engineering Structures, 2025)

Research progress of high-strength self-healing polymer materials: Balance between mechanical strength and self-healing efficiency - Zhi-Hui Yan; Hua-Xin Huang; Guo-Quan Ding; Shan-Shan Dong; Ke-Jin Jiang; Yu-Ying Li; Yang Liu; Yan Jiang; Shuang-Fei Wang; Guo-Hua Hu; Jun Du; Shi-Xian Zhang; et al. (Chemical Engineering Journal, 2025)

Identification, expression analysis, and functional verification of three opsin genes related to the phototactic behaviour of Ostrinia furnacalis - Mei Huang; Jian‐Yu Meng; Xue Tang; Long‐Long Shan; Chang‐Li Yang; Chang‐Yu Zhang (Molecular Ecology, 2025)
Ostrinia furnacalis is a disreputable herbivorous pest that poses a serious threat to corn crops. Phototaxis in nocturnal moths plays a crucial role in pest prediction and control. Insect opsins are the main component of insect visual system. However, the inherent molecular relationship between phototactic behaviour and vision of insects remains a mystery. Herein, three opsin genes were identified and cloned from O. furnacalis ( OfLW , OfBL , and OfUV ). Bioinformatics analysis revealed that all opsin genes had visual pigment (opsin) retinal binding sites and seven transmembrane domains. Opsin genes were distributed across different developmental stages and tissues, with the highest expression in adults and compound eyes. The photoperiod‐induced assay elucidated that the expression of three opsin genes in females were higher during daytime, while their expression in males tended to increase at night. Under the sustained darkness, the expression of opsin genes increased circularly, although the increasing amplitude in males was lower when compared with females. Furthermore, the expression of OfLW , OfBL , and OfUV was upregulated under green, blue, and ultraviolet light, respectively. The results of RNA interference showed that the knockout of opsin genes decreased the phototaxis efficiency of female and male moths to green, blue, and ultraviolet light. Our results reveal that opsin genes are involved in the phototactic behaviour of moths, providing a potential target gene for pest control and a basis for further investigation on the phototactic behaviour of Lepidoptera insects.

Enhanced scavenging and recovery of low-concentration phosphate from secondary effluents using lanthanum-incorporated layered double hydroxide composites - Sujie Shan; Xingning Huang; Zhenyu Yang; Jie Ji; Zhihao Chen; Chongming Wang; Xinpeng Xu; Xi Li; Yao Xu; Songqi Liu; Boling Li; Dapeng Li (Process Safety and Environmental Protection, 2025)

In Vitro metabolism of six representative organic UV stabilizers (OUVs) in marine fish liver microsomes: Kinetics, mechanisms and bioaccumulation evaluation - Yuchen Wang; Qianyi Huang; Siqi Zhang; Shan Liu; Hengxiang Li; Xiaodong Wang; Yan Wang; Rui Hou; Xiangrong Xu (Journal of Hazardous Materials, 2025)

A multi-stochastic fractional programming for sustainable forestry ecological restoration: Managing uncertainties in Kashgar Region, Xinjiang - Yi Bai; Guohe Huang; Dencheng Han; Bin Luo; Yongping Li; Shan Zhao (Ecological Modelling, 2025)

In-situ passivation of perovskite films by parallel surface adsorption of dual-active-site ammonium cations for high-performance inverted perovskite solar cells - Guanlin Li; Zebing Gao; Guogen Huang; Jinxing He; Kangbo Sun; Xinting Wang; Haohua Wu; Chuanlin Gao; Xianghui Zeng; Xianfang Zhou; Hanlin Hu; Yunfei Hu; et al. (Chemical Engineering Journal, 2025)

Harnessing the MYB51/SWEET20 module to increase soybean yield by facilitating sugar supply to sink organs - Jiafang Shen; Dong Cao; Songli Yuan; Qingnan Hao; Hongli Yang; Yi Huang; Lihong He; Jialing Yuan; Zhonglu Yang; Shuilian Chen; Zhihui Shan; Wei Guo; et al. (Plant Cell Reports, 2025)

Characteristics and evolution of mass-transport complex since Late Miocene in the Zengmu and Beikang basins, southern South China Sea - Shuqin Huang; Ming Su; Haiteng Zhuo; Li Zhang; Shan Liu; Zhi Lin Ng; Zhixuan Lin; Boda Zhang; Kunwen Luo; Li’e Lin (Journal of Oceanology and Limnology, 2025)

An innovative red-emitting nickel-doped carbon dot for simultaneous detection of Fe(III) and pyrophosphate ions, coupled with synergistic photothermal/photodynamic cancer therapy - Shan Huang; Wenqian Zhang; Bo Li; Guixin Li; Wei Ni; Yi Fang; Qi Xiao (Analytica Chimica Acta, 2025)

Genome-wide identification, expression analysis and transcriptional regulation of major histocompatibility complex class I genes in mandarin fish Siniperca chuatsi - Jing Hou; Min Chang Li; Lu Qi; Wei Hao; Lan Hao Liu; Zhen Gan; Bei Huang; Wen Shu Huang; Li Wang; Li Li; Shan Nan Chen; Pin Nie (Aquaculture, 2025)

Searching for neutrinoless double-beta decay of 136 Xe with PandaX-4T - Shu Zhang; Zihao Bo; Wei Chen; Xun Chen; Yunhua Chen; Zhaokan Cheng; Xiangyi Cui; Yingjie Fan; Deqing Fang; Zhixing Gao; Lisheng Geng; Karl Giboni; et al. (Science Bulletin, 2025)

Linking gut microbiome profiles and white matter integrity to social behavior in young autistic children: from the perspective of individual variation - Xinyue Huang; Weixing Zhao; Rui Feng; Yuanyue Zhou; Jia Wang; Jinming Xiao; Lei Li; Xiaolong Shan; Yu Feng; Yating Ming; Jing Cao; Xiaodong Kang; et al. (Science Bulletin, 2025)

Exploring the phytotoxicity mechanisms of PET nanoplastics and 6:2 FTSA in water hyacinth under individual and combined exposure scenarios - Zhiheng Li; Zhangchao Yao; Shuping Wang; Haohua Ni; Luming Xiao; Zhixiu Huang; Huijun Liu; Shanying He; Shan Jin; Hainan Lu; Jie Chen (Journal of Hazardous Materials, 2025)

Efflux pumps of Pseudomonas aeruginosa and their regulatory mechanisms underlying multidrug resistance - Wen-Ru Li; Zhi-Qing Zhang; Kang Liao; Qing-Shan Shi; Xu-Bin Huang; Xiao-Bao Xie (International Biodeterioration & Biodegradation, 2025)

Facile and green synthesis of nanocarriers from chondroitin sulfate-based and whey protein isolate with improved stability and biocompatibility for anthocyanins protection - Zixuan Li; Zhipeng Gao; Donglin Su; Zhipeng Su; Yanjiao Fu; Wenbin Xiao; Fuhua Fu; Gaoyang Li; Lvhong Huang; Jiajing Guo; Yang Shan (Food Chemistry, 2025)

A fluorescent aptasensor for kanamycin detection in milk, seafood and water samples using DNA-AgNCs and exonuclease I-assisted recycling amplification strategy - Dong Xu; Lei Shan; Bei Guo; Jing Wang; Qiang Huang; Shujun Wang; Fuhou Li; Shaojie Wu; Weixia Wang; Jinri Chen (Food Chemistry, 2025)

Greenness, nighttime light, and couple fecundability: A national cohort study between 2014 and 2020 - Mengyao Li; Xinghou He; Bin Zhang; Hongbing Xu; Jianbin Wu; Xuyang Shan; Ya Zhang; Huiying Xu; Hongguang Zhang; Yuan He; Yan Fang; Zuoqi Peng; et al. (Environmental Research, 2025)

Enhanced thermotolerance via overexpression of a stromal ascorbate peroxidase in Nannochloropsis oceanica - Shan Wu; Yiting She; Xitao Chen; Xingwei Huang; Tao Xu; Congcong Miao; Qianyi Wu; Zheng Li; Chengcheng Li; Yuhui Cheng; Yi Xin (Plant Cell Reports, 2025)

Modulating JAK2/STAT3 signaling by quercetin in Qiling Baitouweng Tang: a potential therapeutic approach for diffuse large B-cell lymphoma - Xin-Zhuo Zhan; Tian-Hua Wei; Chen Huang; Hui Yu; Xiao-Li Chen; Xiang-Tu Kong; Zhi-Hao Shang; Shan-Liang Sun; Meng-Yi Lu; Hai-Wen Ni (Molecular Diversity, 2025)

Protein Kinase C Epsilon Overexpression Protects the Heart Against Doxorubicin-Induced Cardiotoxicity Via Activating SIRT1 - Danyong Liu; Chunyan Wang; Yao Chen; Xiaolei Huang; Yajie Wen; Shan Duan; Yin Cai; Xia Li; Jianfeng He; Kaijia Han; Ting Li; Yuantao Li; et al. (Cardiovascular Toxicology, 2025)
Doxorubicin (DOX)-induced cardiotoxicity (DIC) is known to be associated with reduction of cardiac protein kinase C epsilon (PKC-ε). PKC-ε promotes cell survival and protects hearts against various stresses. However, it is unclear whether or not the reduction in cardiac PKC-ε expression plays a causal role in DIC and in particular the potential underlying mechanism whereby PKC-ε may protect against DIC. C57BL/6 mice (8–10-week-old) were either treated with DOX administered intraperitoneally for a duration of 4 weeks to produce cardiotoxicity, or untreated in which mice received the same volume of saline. In vitro, neonatal rat ventricle cardiomyocytes were exposed to DOX for 24 h in the absence or presence of adenovirus overexpressing PKC-ε. Cardiomyocytes in a subgroup were treated with sirtuin-1 (SIRT1) selective inhibitor Ex527. Four weeks after DOX, cardiac contractile function was decreased concomitant with increased serum CK-MB and LDH levels as well as increases in Bax-to-Bcl-2 ratio and Cleaved Caspase 3 proteins expression, while PKC-ε and Sirt1 protein expressions were significantly decreased. In vitro, DOX reduced cardiomyocyte PKC-ε and SIRT1 protein expression, decreased cardiomyocyte viability, and increased LDH release with concomitant increases in oxidative stress and apoptosis. These changes were attenuated by overexpression of PKC-ε. IP study showed that PKC-ε could directly or indirectly bind SIRT1 in cardiomyocytes, and the protect effects of PKC-ε were further canceled by SIRT1 inhibition. In conclusion, activating SIRT1 may represent a major mechanism whereby PKC-ε protects the heart against DOX-induced cell apoptosis and oxidative stress. Graphical Abstract Dox induces cardiotoxicity via inhibiting PKC-epsilon/Sirt1 signaling which can be reversed by PKC-epsilon overexpression.

Microenvironmental profile of patients with refractory otomycosis: a cohort study and post hoc analysis - Shun Ding; Yunzhong Zhang; Huiqian Yu; Xiaoling Huang; Shihang Mao; Xiao Xiao; Yusu Ni; Huawei Li; Shan Sun (Mycological Progress, 2025)

Mortality risk of short-term air pollution exposure in urban and rural Chinese populations: A nationwide time-stratified case-crossover study, 2008–2020 - Yunning Liu; Hongbing Xu; Xuyang Shan; Xinpeng Guan; Lijun Wang; Xinghou He; Jiangmei Liu; Jinling You; Rongshan Wu; Jianbin Wu; Bin Zhang; Jinlei Qi; et al. (International Journal of Hygiene and Environmental Health, 2025)

Tracing the Changjiang-derived sediments along the southeast coast of China during the Holocene - Yalong Li; Xin Shan; Xiangtong Huang; Zhanghua Wang; Jianhua Gao; Ping Yin; Quanhong Zhao; Juan Xu; Zhen Song; Shouye Yang (Global and Planetary Change, 2025)

Experimental Study on Factors Influencing Interaction Behaviors of Hydraulic Fractures and Coal–Rock Interface: Stress, Interface and Perforation - Changzheng Lu; Zhaolong Ge; Zhe Zhou; Quangui Li; Jianming Shangguan; Shan Huang; Qinglin Deng (Rock Mechanics and Rock Engineering, 2025)

Avian influenza A(H5N6) virus detected during live-poultry market surveillance linked to a human infection in Changsha, China, from 2020 to 2023 - Zheng Huang; Rusheng Zhang; Dong Yao; Huiyuan Fu; Lingzhi Li; Shan Xiao; Xinhua Ou; Mingzhong Xu; Qing-Bin Lu; Xuewen Yang (Archives of Virology, 2025)

Protosappanin B activates the Wnt pathway to protect against glucocorticoid-induced osteoblast inhibition and enhance bone formation - Jigeng Fan; Yahui Wang; Houzhi Yang; Shaoyuan Huang; Yuan Ma; Jie Guo; YuTao Jia; Ying Zhang; Yonggang Fan; Donglun Xiao; Jiawei Zhang; Jianwei Li; et al. (Chemico-Biological Interactions, 2025)

Identification of quinoa B3 gene family and its expression pattern in response to low temperature stress - Lingyuan Zhang; Yanbo Xia; Guofei Jiang; Xuqin Wang; Yutao Bai; Ping Zhang; Junna Liu; Li Li; Hanxue Li; Liubin Huang; Shan Zhang; Peng Qin (Genetic Resources and Crop Evolution, 2025)

Seismic response analysis of buried pipelines with varying stiffness by shaking table tests - Hongyu Chen; Jie Cui; Yadong Li; Zhiyong Ouyang; Xiangyun Huang; Yi Shan (Earthquake Engineering and Engineering Vibration, 2025)

The antinociceptive and anti-alpha-glucosidase effects of glucosides from Hemiphragma heterophyllum Wall. - Chun-Fang Wen; Yu-Xiao Li; Ke-Xin Nie; Qiu He; Ya Lu; Zi-Liang Wang; Xi-Shan Bai; Yan-Hong Li; Xiang-Zhong Huang (Natural Product Research, 2025)

Fossil pods of tropical tree Peltophorum (Caesalpinioideae, Fabaceae) from southwestern China - Yi-Shan Zhao; Teng-Xiang Wang; Shu-Mei Xiao; Shu-Feng Li; Jian Huang (Review of Palaeobotany and Palynology, 2025)

The association between anthropogenic heat and parent-report symptoms of childhood attention deficit hyperactivity disorder in China: A novel perspective reflecting climate change - Tao Yu; Yue Wen; Pei-Pei Dong; Ming-Kun Sun; Samantha E. Qian; Mario Schootman; Michael G. Vaughn; Shu-Li Xu; He-Hai Huang; Feng-Wen Shan; Shi-Fu Zhu; Jing-Yao Wang; et al. (International Journal of Hygiene and Environmental Health, 2025)

Peficitinib suppresses diffuse-type tenosynovial giant cell tumor by targeting TYK2 and JAK/STAT signaling - Shan Lu; Chenxi Cao; Wenjia Zhang; Jiayi Li; Jingli Yang; Zisheng Huang; Zhijun Wu; Baitao Liu; Hongjie Huang; Haijun Wang; Yongjian Wang; Dingge Liu; et al. (Science China Life Sciences, 2025)

Electroactive bacteria-established long-distance electron transfer to oxygen facilitates bio-transformation of dissolved organic matter for sediment remediation - Yinxiu Liang; Meijun Dong; Shan Yang; Lizhou Lin; Haobin Huang; Daobo Li; Min Ji; Meiying Xu (Water Research, 2025)

Intra-urban comparison of hazardous VOCs in Hong Kong: Source apportionment and integrated risk assessment - Xiangyunong Cao; Dasa Gu; Hao Sun; Ka Fung Leung; Yuchen Mai; Xin Li; Wai Ming Chan; Sin Ka Mak; Zhenxing Liang; Wentai Zhang; Yisheng Zhang; Shan Huang; et al. (Sustainable Cities and Society, 2025)

Warming effects on the emission pathways of N2O and CH4 and the role of water column in shallow eutrophic lakes - Rongwei Xiong; Ming Chen; Yong Li; Guangbao Sun; Jinquan Huang; Yan Xue; Zeyuan Shan; Tianqi Li (Science of The Total Environment, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Migration of fungicides, antibiotics and resistome in the soil-lettuce system - Chenyu Huang; Minrong Cui; Tongxin Li; Conglai Zheng; Mengting Qiu; Mei Shan; Baotong Li; Luqing Zhang; Yunlong Yu; Hua Fang (Journal of Hazardous Materials, 2025)

Exposure to perchlorate and cardiovascular disease in China: A community-based cross-sectional study and benchmark dose estimation - Lei King; Lili Xia; Juan Chen; Wanyi Li; Qiang Wang; Yue Huang; Pei Wang; Xiaoling Liang; Yonggang Li; Liangkai Chen; Zhilei Shan; Xiaolin Peng; et al. (Environmental Pollution, 2025)

OCTN2 expression and function in the Sertoli cells of testes from patients with non-obstructive azoospermia - Dong Li; Nan Jiang; Minjia Pan; Linzi Ma; Yunchong Huang; Xiaoheng Xu; Xinyan Yang; Yongtong Zhu; Hua Shi; Shan-Chao Zhao (Journal of Molecular Histology, 2025)

A coupled hydro-mechanical damage constitutive model for carbonate rocks subjected to karst erosion - Chaoyuan Yong; Chen Wang; Yujun Zuo; Aoli Li; Zichen Li; Shan Jiang; Xinxin Huang (Carbonates and Evaporites, 2025)

Changes of Yancheng coastline near 20 years based on remote sensing technology - Yu Song; Shuang Yang; Dongxu Li; Yubao Shao; Jie Cheng; Xingxing Shan; Li Cao; Silong Li; Chao Xie; Li Shan; Delong Tian; Hao Wang; et al. (Marine Georesources & Geotechnology, 2025)

Unveiling the effects of artificial intelligence and green technology convergence on carbon emissions: An explainable machine learning-based approach - Tianlong Shan; Shuai Feng; Kaijian Li; Ruidong Chang; Ruopeng Huang (Journal of Environmental Management, 2025)

Jellyfish–mimetic solar evaporator with polyelectrolyte skeleton for sustainable desalination under higher salinity - Shan Zhai; Fang Yu; Naila Arshad; Suji Huang; Junyang Tao; Changwen Li; Liangyou Lin; Jingwen Qian; Muhammad Sultan Irshad; Xianbao Wang (Desalination, 2025)

Enhanced low-temperature CO2 methanation performance over mesoporous Y2O3 confined Ni catalysts - Haifeng Fan; Di Xu; Kaidi Liu; Guoqiang Hou; Yangyang Li; Siyi Huang; Ke Wu; Yanfei Xu; Ruoting Shan; Zhenxuan Zhang; Mingyue Ding (Chemical Engineering Journal, 2025)

Kv3.1 Interaction with UBR5 Is Required for Chronic Inflammatory Pain - Ying Zeng; Meng-Lan Sun; Di Liu; Yue Huang; Shan Xie; Ya-Xuan Zhao; Zi-Xuan Wu; Ya Liu; Gan Ma; Ling Xie; Yu-Tao Dang; Ling-Yun Hao; et al. (Molecular Neurobiology, 2025)

Protective Effect of Selenium-enriched Peptide from Cardamine violifolia on Ethanol-induced L-02 Hepatocyte Injury - Rongrui Ling; Chaodong Du; Yue Li; Shan Wang; Xin Cong; Dejian Huang; Shangwei Chen; Song Zhu (Biological Trace Element Research, 2025)

Association of anthropogenic heat with asthma and related symptoms among children in China: A novel index reflecting climate change - Feng-Wen Shan; Xuan Liu; Ming-Kun Sun; Zhengmin Qian; Michael G. Vaughn; Niraj R. Chavan; Shu-Li Xu; He-Hai Huang; Zhao-Huan Gui; Ru-Qing Liu; Li-Wen Hu; Li-Zi Lin; et al. (Sustainable Cities and Society, 2024)

Green synthesis of nanoscale zero-valent iron impregnated walnut shell biochar as efficient adsorbent for metal(loid)s purification: Performance and mechanism insight - Junhao Huang; Zhangtao Li; Shengdao Shan; Malik Tahir Hayat; Jun Meng (Journal of Water Process Engineering, 2024)

Cadmium uptake and transport in vegetables near a zinc–lead mine: Novel insights from Cd isotope fractionation - Wen Liao; Yuanying Huang; Songxiong Zhong; Longlong Zhang; Kai Yu; Shan Yu; Pengji Su; Chao Jin; Lei Yang; Fangbai Li (Journal of Hazardous Materials, 2024)

Xenobiotic metabolism activity of gut microbiota from six marine species: Combined taxonomic, metagenomic, and in vitro transformation analysis - Siqi Zhang; Rui Hou; Yuchen Wang; Qianyi Huang; Lang Lin; Hengxiang Li; Shan Liu; Zhijian Jiang; Xiaoping Huang; Xiangrong Xu (Journal of Hazardous Materials, 2024)

Dynamics of nitrogen mineralization and nitrogen cycling functional genes in response to soil pore size distribution - Danni Li; Yi Li; Shuihong Yao; Hu Zhou; Shan Huang; Xianlong Peng; Yili Meng (European Journal of Soil Biology, 2024)

Circular reinforced concrete columns strengthened by combined square steel tube and concrete jackets subjected to eccentric load - Yuhong Yan; Shan Li; Yue Huang; Yiyan Lu; Xiaobo Zhao (Engineering Structures, 2024)

Free-standing, robust, hyperconnective hybrid nanofiber nonwovens enabled by interpenetrating network for oily aerosols purification - Weitao Zhou; Yiming Li; Zeng Qu; Sen Li; Ting Wu; Jingliang Li; Tingting Shi; Jikai Chen; Boyu Li; Haitao Huang; Shan Du (Chemical Engineering Journal, 2024)

OsCactin positively regulates the drought stress response in rice - Jinqiu Huang; Mingqiang Zhu; Zhihui Li; Shan Jiang; Shuang Xu; Mingyue Wang; Zhaohui Chu; Menghao Zhu; Zhihong Zhang; Wenchao Huang (Plant Cell Reports, 2024)

Sporelings and growth of the marine red alga, Gelidium elegans (Gelidiaceae), from Northern Taiwan - Showe-Mei Lin; Shih-Jhe Chen; Pin-Yu Huang; Li-Chia Liu; Yu-Shan Chiou (Journal of Applied Phycology, 2024)

Changes in the metabolic score for insulin resistance index for risk prediction of stroke in middle-aged and older Chinese population - Tingting Wang; Zhiheng Yi; Yuhan Tan; Yangshen Huang; Tengli Li; Shan Gao; Yaoling Wu; Weiduan Zhuang; Shaowei Guo (EPMA Journal, 2024)

Recent selection and introgression facilitated high-altitude adaptation in cattle - Yang Lyu; Fuwen Wang; Haijian Cheng; Jing Han; Ruihua Dang; Xiaoting Xia; Hui Wang; Jincheng Zhong; Johannes A. Lenstra; Hucai Zhang; Jianlin Han; David E. MacHugh; et al. (Science Bulletin, 2024)

T cell senescence may contribute to immunothrombosis via Th17 immune transition in COVID-19 - Wenxing Li; Rui Qian; Zhaoming Zhou; Lei Wen; Quan Yin; Xiang Zhou; Xiaowei Li; Jie Cheng; Xinlu Zhang; Xin Zeng; Zhuoya Wang; Yingying Huang; et al. (Science Bulletin, 2024)

Optimization of kW-scale methanol reforming high-temperature proton exchange membrane fuel cells with efficient waste heat utilization - Ruhang Zhang; Hongxiang Zheng; Chuandong Li; Feng Huang; Xinhai Yu; Shan-dong Tu (Fuel, 2024)

Experimental and numerical investigation of bias performance of steel fiber-reinforced GRC-CFFT columns - Dongming Huang; Zhenzhen Liu; Yiyan Lu; Wentao Ma; Shan Li (Engineering Structures, 2024)

Constructing efficient Pd/Al2O3 catalyst for reverse water-gas shift via alkali-modification - Xi-Guang Wang; Lu-Yang Qiao; Li-Yuan Xu; Yun-Yun Zeng; Zhi-Shen Huang; Shan-Shan Zong; Jin-Xiang Wang; Zhang-Feng Zhou; Yuan-Gen Yao (Chemical Engineering Journal, 2024)

Single nickel atoms anchored on porous N-doped nanocarbon with dual reaction sites for highly-efficient transfer hydrogenation of furfural to furfuryl alcohol - Tianyi Guo; Yingying Luo; Huangjuan Li; Shan Huang; Yanjuan Zhang; Zuqiang Huang; Huayu Hu; Tao Gan (Chemical Engineering Journal, 2024)

Synchronous sequestration of inorganic and organic phosphorus from eutrophic surface water and sediments via recoverable La-CaO2@HNTs/SA hydrogel beads - Chongming Wang; Sujie Shan; Zhengyu Yang; Xinpeng Xu; Xingning Huang; Xi Li; Songqi Liu; Boling Li; Yao Xu; Dapeng Li (Chemical Engineering Journal, 2024)

The role of urban green space landscape patterns in the synergistic prevention of PM2.5 and ozone pollution: A case study in Shenyang city, China - Yu Li; Leichang Huang; Siwen Li; Min Cao; Peng Tan; Qiaochu Wang; Huan Meng; Shan Yin; Weikang Zhang (Atmospheric Pollution Research, 2024)

Acinetobacter corruptisaponis sp. nov., Isolated from a Spoiled Bath Lotion - Ying-Si Wang; Gang Zhou; Hong-Bing Tao; Lei Gao; Bao-Zhu Fang; Xiu-Jiang Yang; Hong Peng; Xia Wen; Xiao-Mo Huang; Jie Wang; Wen-Jun Li; Qing-Shan Shi; et al. (Current Microbiology, 2024)

Correction to: Effects of Long-term Climate Change on Typhoon Rainfall Associated with Southwesterly Monsoon Flow near Taiwan: Mindulle (2004) and Morakot (2009) - Chung-Chieh Wang; Li-Shan Tseng; Chien-Chang Huang; Pi-Yu Chuang; Nan-Chou Su; Cheng-Ta Chen; Shih-How Lo; Kazuhisa Tsuboki (Asia-Pacific Journal of Atmospheric Sciences, 2024)

Soil pH Determines Nitrogen Effects on Methane Emissions From Rice Paddies - Junqi Tang; Haoyu Qian; Xiangcheng Zhu; Zhuoshu Liu; Yakov Kuzyakov; Jianwen Zou; Jinyang Wang; Qiang Xu; Ganghua Li; Zhenghui Liu; Songhan Wang; Weijian Zhang; et al. (Global Change Biology, 2024)
Rice paddies account for approximately 9% of human‐induced methane (CH 4 ) emissions. Nitrogen (N) fertilization affects CH 4 emissions from paddy soils through several mechanisms, leading to conflicting results in field experiments. The primary drivers of these N‐related effects remain unclear and the contribution of N fertilization to CH 4 emissions from the rice paddies has not yet been quantified for global area. This uncertainty contributes to significant challenges in projecting global CH 4 emissions and hinders the development of effective local mitigation strategies. Here, we show through a meta‐analysis and experiments that the impact of N fertilization on CH 4 emissions from rice paddies can be largely predicted by soil pH. Specifically, N fertilization stimulates CH 4 emissions most strongly in acidic soils by accelerating organic matter decomposition and increasing the activities of methanogens. Accounting for the interactions between soil pH and N fertilization, we estimate that N fertilization has raised current area‐scaled and yield‐scaled CH 4 emissions across the total global paddy area by 52% and 8.2%, respectively. Our results emphasize the importance of alleviating soil acidification and sound N management practices to mitigate global warming.

Trifluoro-Icaritin Ameliorates Neuroinflammation Against Complete Freund’s Adjuvant-Induced Microglial Activation by Improving CB2 Receptor-Mediated IL-10/β-endorphin Signaling in the Spinal Cord of Rats - Guangsen Liu; Dandan Jia; Weiwei Li; Zhihua Huang; Reai Shan; Cheng Huang (Journal of Neuroimmune Pharmacology, 2024)

Accurately estimate soybean growth stages from UAV imagery by accounting for spatial heterogeneity and climate factors across multiple environments - Yingpu Che; Yongzhe Gu; Dong Bai; Delin Li; Jindong Li; Chaosen Zhao; Qiang Wang; Hongmei Qiu; Wen Huang; Chunyan Yang; Qingsong Zhao; Like Liu; et al. (Computers and Electronics in Agriculture, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

ESR chronology of the Quaternary sedimentary sequence of the Shinaimiao borehole in Hebi City, Henan Province, China - Hao Ji; Zhong-shan Shen; Chun-Ru Liu; Xiong-Nan Huang; Xiao-Ping Yang; Chuan-Yi Wei; Xin-Xiu Li; Qing Zhou; Gong-Ming Yin (Quaternary Geochronology, 2024)

BrARR10 contributes to 6-BA-delayed leaf senescence in Chinese flowering cabbage by activating genes related to CTK, GA and ABA metabolism - Ci-mei Wang; Ze-xiang Zeng; Zong-li Liu; Jian-hua Zhu; Xin-guo Su; Ri-ming Huang; Wei Wei; Wei Shan; Jian-fei Kuang; Wang-jin Lu; Jian-ye Chen; Ying-ying Yang (Postharvest Biology and Technology, 2024)

Stabilizing methyl ferulate with nanosystem enhances its antifungal activity against Alternaria alternata in vitro and in vivo - Saiqing Xu; Shuai Ge; Ying Xie; Jing Cheng; Ke Ding; Huan Li; Hua Huang; Zisheng Luo; Yang Shan; Shenghua Ding (Postharvest Biology and Technology, 2024)

The nicotine demethylase CYP82E4 is essential for the formation of red dapples on flue-cured leaves of cherry-red tobacco - Fei Liu; Xueyi Sui; Yong Li; Yihan Zhang; Lu Zhao; Jiahong Liu; Shuanglü Shan; Feng Li; Xiaolong Chen; Long Zhang; Kun Huang; Yuping Ma; et al. (Plant Science, 2024)

Lignin-derived carbon as rapid charge-transfer bridge for efficient solar-driven H2O2 production over CN/Mxene heterojunction - Jiashu Li; Jun Yu; Shengye Wu; Tianshang Shan; Xia Xu; Fengshan Zhang; Liulian Huang; Lihui Chen; He Xiao (Journal of Environmental Chemical Engineering, 2024)

Performance, reaction mechanism and modification methods for Mn-based CO-SCR catalysts: A review - Weilong Huang; Siyi Yang; Xiaodi Li; Chunlian Ding; Shan Ren; Sicheng Li; Haoran Zhang; Xinyu Pi; Xi-Tao Yin (Journal of Environmental Chemical Engineering, 2024)

Exploring organophosphate ester contamination and distribution in food: A meta-analysis - Wenjun Li; Junlong Chen; Qianqian Bie; Xianggui Chen; Yukun Huang; Kaihui Zhang; Shan Qian (Food Chemistry, 2024)

Citrus aurantium L. 'Daidai' physiological premature fruit drop relieves obesity in high-fat-diet-fed mice via modulating lipid metabolism and gut microbiota - Mingfang Peng; Chao Wang; Zhipeng Gao; Fuhua Fu; Gaoyang Li; Donglin Su; Lvhong Huang; Jiajing Guo; Yang Shan (Food Bioscience, 2024)

Bioactivities evaluation of an endophytic bacterial strain Bacillus tequilensis QNF2 inhibiting apple ring rot caused by Botryosphaeria dothidea on postharvest apple fruits - Yonghong Huang; Jinghui Li; Xiaoying Shan; Hanting Wang; Yanxin Duan (Food Microbiology, 2024)

Assessing health risks from bioaccessible PM2.5-bound toxic metals in Nanchang metro: Implications for metro workers and emissions control - Shan Huang; Minglei Han; Peixian Chen; Weiwei Feng; Guobo Li; Hongxiang Zhang; Honggen Peng; Ting Huang (Environmental Research, 2024)

The LINGO-1-deficient neural stem cell-derived neural tissueoid showed enhanced retention and neuronal relay in the transected spinal cord - Ge Li; Li-Jun Huang; Bao Zhang; Shu Liu; Jing-Hua Liang; Ying Ding; Xiang Zeng; Bi-Qin Lai; Yuan-Huan Ma; Ya-Qiong Wang; Rui Wang; Hong-Bo Zhang; et al. (Chemical Engineering Journal, 2024)

The impact of street-scale built environments on urban park visitations: A case study in Wuhan - Wenting Zhang; Haochun Guan; Shan Li; Bo Huang; Wuyang Hong; Wenping Liu (Applied Geography, 2024)

Photoelectron‐promoted metabolism of sulphate‐reducing microorganisms in substrate‐depleted environments - Chao Zhong; Anhuai Lu; Hailiang Dong; Shan Huang; Liang Shi; Yanan Shen; Yangjian Cheng; Yiran Dong; Xiangzhen Li; Jie Xu; Jinren Ni; Michael F. Hochella; et al. (Environmental Microbiology, 2024)
Sulphate‐reducing microorganisms, or SRMs, are crucial to organic decomposition, the sulphur cycle, and the formation of pyrite. Despite their low energy‐yielding metabolism and intense competition with other microorganisms, their ability to thrive in natural habitats often lacking sufficient substrates remains an enigma. This study delves into how Desulfovibrio desulfuricans G20, a representative SRM, utilizes photoelectrons from extracellular sphalerite (ZnS), a semiconducting mineral that often coexists with SRMs, for its metabolism and energy production. Batch experiments with sphalerite reveal that the initial rate and extent of sulphate reduction by G20 increased by 3.6 and 3.2 times respectively under light conditions compared to darkness, when lactate was not added. Analyses of microbial photoelectrochemical, transcriptomic, and metabolomic data suggest that in the absence of lactate, G20 extracts photoelectrons from extracellular sphalerite through cytochromes, nanowires, and electron shuttles. Genes encoding movement and biofilm formation are upregulated, suggesting that G20 might sense redox potential gradients and migrate towards sphalerite to acquire photoelectrons. This process enhances the intracellular electron transfer activity, sulphur metabolism, and ATP production of G20, which becomes dominant under conditions of carbon starvation and extends cell viability in such environments. This mechanism could be a vital strategy for SRMs to survive in energy‐limited environments and contribute to sulphur cycling.

MgO-based supersulfated cement with different industrial by-product gypsum: Experiments and molecular dynamics simulation - Jiang-shan Li; Wei Zhang; Xiao Huang; Lei Lang; Chi Sun Poon; Qiang Xue (Science of The Total Environment, 2024)

A novel method of fuel consumption prediction for wing-diesel hybrid ships based on high-dimensional feature selection and improved blending ensemble learning method - Tian Lan; Lianzhong Huang; Ranqi Ma; Zhang Ruan; Shan Ma; Zhongwei Li; Haoyang Zhao; Cong Wang; Rui Zhang; Kai Wang (Ocean Engineering, 2024)

Electro-nitrification coupled with biological denitrification achieves efficient nitrogen removal from rare earth mine ammonia-nitrate wastewater - Qiming Li; Luanqi Zhou; Bing Li; Jing Liu; Shan Huang; Chenglong Zou; Zhanmeng Liu; Meng Zhang; Huimin Zhang (Journal of Water Process Engineering, 2024)

Spatial variation, emissions, transport, and risk assessment of organophosphate esters in two large petrochemical complexes in southern China - Wen-Qing Mo; Zhen-Shan Huang; Qi-Qi Li; Jun Yao; Chun-You Zhu; Hui-Ying Guo; Yuan Zeng; She-Jun Chen (Journal of Environmental Management, 2024)

Slenderness effects on concrete-filled square steel tube columns strengthened with CFRP grid-reinforced ECC matrix - Yuhong Yan; Wentao Ma; Yiyan Lu; Shan Li; Yue Huang (Engineering Structures, 2024)

Axial performance of concrete-filled GFRP tube columns jacketed by outer stainless steel tube and sandwiched concrete - Yue Huang; Yiyan Lu; Pengpeng Wang; Shan Li; Yifan Jiao (Engineering Structures, 2024)

Carboxymethylcellulose and rare earth metal cation self-assembly: Tunable encapsulation of carbon dots in a multifunctional transparent film - Zhihao Shan; Jiayi Huang; Yuling Huang; Yuping Zhou; Yiqun Li (Chemical Engineering Journal, 2024)

New approach for raw biogas: Production of single cell protein by sulfide-tolerant methane-oxidizing bacteria consortia - Hai-Ming Huang; Zhi-Xin Xue; Yu-Feng Jiang; Rui Li; Rong-Bo Guo; Xiao-Lei Fan; Shan-Fei Fu (Chemical Engineering Journal, 2024)

Molecular profiling of core immune-escape genes highlights TNFAIP3 as an immune-related prognostic biomarker in neuroblastoma - Linyu yang; Kai Huang; Lijian Cao; Yue Ma; Suwen Li; Jianwu Zhou; Zhenzhen Zhao; Shan Wang (Inflammation Research, 2024)

Complex ammonium oxidation demands visualized resolution - Zhihao Chen; Yonghong Wu; Jan Dolfing; Shunyao Zhuang; Baozhan Wang; Dan Li; Shan Huang; Bruce E. Rittmann (Science Bulletin, 2024)

Artificial phytoremediation solar interface evaporator for efficient heavy metal salt separation and saline soil remediation - Yaping Xu; Chenyang Dang; Xiangkun Elvis Cao; Yunteng Cao; Jiu Huang; Yuxiang Xu; Minghui Shan; Rui Liu; Peng Li; Guiyin Xu; Meifang Zhu (Journal of Environmental Chemical Engineering, 2024)

Innovative insights into organic nitrogen degradation through protein family domains analysis in chicken and pig manure composting using metagenomic sequencing - Lin Zhu; Caihong Huang; Lipin Li; Simiao Wang; Xinxin Wu; Guangchun Shan; Yu Tian (Bioresource Technology, 2024)

Three new chromones from the whole plants of Chamaecrista rotundifolia and their anti-rotavirus activities - Pei-Song Yang; Xin-Yan He; Shan-Shan Li; De-Quan Huang; Si-Yu Shen; Xiao-Shan Liu; Yue-Yu Ma; Miao Dong; Min Zhou; Feng-Xian Yang; Yin-Ke Li (Natural Product Research, 2024)

Evaluation of immunogenicity and protective efficacy of outer membrane vesicles from Salmonella Typhimurium and Salmonella Choleraesuis - Yichen Tian; Shan Huang; Guodong Zhou; Xia Fei; Yu-an Li; Quan Li; Shifeng Wang; Huoying Shi (Veterinary Microbiology, 2024)

Negative impacts of perishable waste biochar to Escherichia coli and exploring potential damage factors - Xuan Gao; Chao Li; Haozhe Zhang; Lingya Jiang; Jing Fang; Min Zhang; Shengdao Shan; Rixiang Huang; Tatiana Minkina; Sudhakar Srivastava (Science of The Total Environment, 2024)

Pseudomonas protegens controlled brown rot (Monilinia fructicola) on peach fruit in postharvest by suppressing fungal development and inducing plant defense-related genes - Xiaoying Shan; Cuifang Zhang; Jinghui Li; Yanxin Duan; Yonghong Huang (Postharvest Biology and Technology, 2024)

Ent-eudesmane sesquiterpenoids with anti-neuroinflammatory activity from the marine-derived fungus Eutypella sp. F0219 - Zhong-Ping Jiang; Rui Su; Meng-Ting Chen; Jun-Yi Li; Han-Yu Chen; Lu Yang; Fei-Fei Liu; Jin Liu; Cong-Jun Xu; Wan-Shan Li; Yong Rao; Ling Huang (Phytochemistry, 2024)

Multiple covalent/hydrogen bonds bridging electron transfer in polymeric carbon nitride for efficient photocatalytic H2O2 production - Jianwen Zhou; Tianshang Shan; Shengye Wu; Jiashu Li; Fengshan Zhang; Liulian Huang; Lihui Chen; He Xiao (Chemical Engineering Journal, 2024)

Moniezia benedeni infection increases IgE+ cells in sheep (Ovis aries) small intestine - Jing Pan; Wan-Ling Yao; Li-Ping Liu; Bao-Shan Wang; Wen-Zhu Chai; Zhen Huang; Xi-Ping Fan; Wan-Hong He; Wen-Hui Wang; Wang-Dong Zhang (Veterinary Parasitology, 2024)

Metabolic signatures of two scleractinian corals from the northern South China sea in response to extreme high temperature events - Shan Huang; Li Luo; Beihua Wen; Xurui Liu; Kefu Yu; Man Zhang (Marine Environmental Research, 2024)

Insights into atmospheric trace gases, aerosols, and transport processes at a high-altitude station (2623 m a.s.l.) in Northeast Asia - Ye Shan; Yujiao Zhu; Yanbi Qi; Yu Yang; Jiangshan Mu; Mingxuan Liu; Hongyong Li; Ji Zhang; Yanqiu Nie; Yuhong Liu; Min Zhao; Xin Zhang; et al. (Atmospheric Environment, 2024)

Retraction Note: Vacuolar protein sorting 35 (VPS35) acts as a tumor promoter via facilitating cell cycle progression in pancreatic ductal adenocarcinoma - Yanzhi Gai; Liheng Qian; Shuheng Jiang; Jun Li; Xueli Zhang; Xiaomei Yang; Hong Pan; Yingna Liao; Huiling Wang; Shan Huang; Shan Zhang; Huizhen Nie; et al. (Functional & Integrative Genomics, 2024)

Effects of warming on greenhouse gas emissions from China’s rice paddies - Nan Zhang; Lin Wang; Xueni Wang; Zhuoshu Liu; Shan Huang; Zihao Wang; Changqing Chen; Haoyu Qian; GangHua Li; Zhenghui Liu; Yanfeng Ding; Weijian Zhang; et al. (Agriculture, Ecosystems & Environment, 2024)

Effects of Long-term Climate Change on Typhoon Rainfall Associated with Southwesterly Monsoon Flow near Taiwan: Mindulle (2004) and Morakot (2009) - Chung-Chieh Wang; Li-Shan Tseng; Chien-Chang Huang; Pi-Yu Chuang; Nan-Chou Su; Cheng-Ta Chen; Shih-How Lo; Kazuhisa Tsuboki (Asia-Pacific Journal of Atmospheric Sciences, 2024)

The death domain-associated protein suppresses porcine epidemic diarrhea virus replication by interacting with signal transducer and activator of transcription 1 and inducing downstream ISG15 expression - Qin Gao; Chuni Zhang; Xiaohan Xu; Xiaoqi Huang; Dekai Jia; Ying Shan; Weihuan Fang; Xiaoliang Li; Jidong Xu (Veterinary Microbiology, 2024)

Cardiorespiratory effects of indoor ozone exposure during sleep and the influencing factors: A prospective study among adults in China - Luyi Li; Wenlou Zhang; Shan Liu; Wanzhou Wang; Xuezhao Ji; Yetong Zhao; Masayuki Shima; Yoshiko Yoda; Di Yang; Jing Huang; Xinbiao Guo; Furong Deng (Science of The Total Environment, 2024)

Experimental and analytical investigation on eccentric performance of circular CFST columns jacketed by concrete-filled square tube - Yue Huang; Yiyan Lu; Shan Li; Yuhong Yan (Engineering Structures, 2024)

GNN-LSTM-based fusion model for structural dynamic responses prediction - Po-Chih Kuo; Yuan-Tung Chou; Kuang-Yao Li; Wei-Tze Chang; Yin-Nan Huang; Chuin-Shan Chen (Engineering Structures, 2024)

A multi-functional CoN-Mo2N heterostructure nanorods for high performance lithium-sulfur batteries - Chun Xu; Xiangli Jiang; Minggang Huang; Wei Luo; Shan Zhang; Shuo Zhao; Guochun Li; Jiabiao Lian (Chemical Engineering Journal, 2024)

Novel insights into the protective effects of leonurine against acute kidney injury: Inhibition of ER stress-associated ferroptosis via regulating ATF4/CHOP/ACSL4 pathway - Ran Cheng; Xiaowan Wang; Lihua Huang; Zhisheng Lu; Aijun Wu; Shan Guo; Chuang Li; Wei Mao; Ying Xie; Peng Xu; Ruimin Tian (Chemico-Biological Interactions, 2024)

High-fat diet impairs gut barrier through intestinal microbiota-derived reactive oxygen species - Nianyi Zeng; Fan Wu; Junqi Lu; Xiang Li; Shaomei Lin; Lang Zhou; Zhongwei Wang; Guangyan Wu; Qingfa Huang; Daowen Zheng; Jie Gao; Shan Wu; et al. (Science China Life Sciences, 2024)

Correlation of Immune-Inflammatory Response System (IRS)/Compensatory Immune-Regulatory Reflex System (CIRS) with White Matter Integrity in First-Episode Patients with Schizophrenia - Mengzhuang Gou; Wei Li; Jinghui Tong; Yanfang Zhou; Ting Xie; Ting Yu; Wei Feng; Yanli Li; Song Chen; Baopeng Tian; Shuping Tan; Zhiren Wang; et al. (Molecular Neurobiology, 2024)

Emergence of a clinical Salmonella enterica serovar 1,4,[5], 12: i:-isolate, ST3606, in China with susceptibility decrease to ceftazidime-avibactam carrying a novel blaCTX-M-261 variant and a blaNDM-5 - Jie Wei; Shimei Shen; Qinghuan Zhang; Jinping Lu; Shenglan Mao; Chunhong Zou; Hua Zhou; YeLin Wei; Xingyi Ou; Jinyu Huang; Deqiang Wang; Xiaobin Li; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Purpose The detection rate of Salmonella enterica serovar 1,4,[5], 12: i: - (S. 1,4,[5], 12: i: -) has increased as the most common serotype globally. A S . 1,4,[5], 12: i: - strain named ST3606 (sequence type 34), isolated from a fecal specimen of a child with acute diarrhea hospitalized in a tertiary hospital in China, was firstly reported to be resistant to carbapenem and ceftazidime-avibactam. The aim of this study was to characterize the whole-genome sequence of S. 1,4,[5], 12: i: - isolate, ST3606, and explore its antibiotic resistance genes and their genetic environments. Methods The genomic DNA of S. 1,4,[5], 12: i: - ST3606 was extracted and performed with single-molecule real-time sequencing. Resistance genes, plasmid replicon type, mobile elements, and multilocus sequence types (STs) of ST3606 were identified by ResFinder 3.2, PlasmidFinder, OriTfinder database, ISfinder database, and MLST 2.0, respectively. The conjugation experiment was utilized to evaluate the conjugation frequency of pST3606-2. Protein expression and enzyme kinetics experiments of CTX-M were performed to analyze hydrolytic activity of a novel CTX-M-261 enzyme toward several antibiotics. Results Single-molecule real-time sequencing revealed the coexistence of a 109-kb IncI1-Iα plasmid pST3606-1 and a 70.5-kb IncFII plasmid pST3606-2. The isolate carried resistance genes, including bla NDM-5 , sul1 , qacE , aadA2 , and dfrA12 in pST3606-1, bla TEM-1B , aac (3)- lld , and bla CTX-M-261 , a novel bla CTX-M-1 family member, in pST3606-2, and aac (6')- Iaa in chromosome. The bla CTX-M-261 was derived from bla CTX-M-55 by a single-nucleotide mutation 751G>A leading to amino acid substitution of Val for Met at position 251 (Val251Met), which conferred CTX-M increasing resistance to ceftazidime verified by antibiotics susceptibility testing of transconjugants carrying pST3606-2 and steady-state kinetic parameters of CTX-M-261. pST3606-1 is an IncI1-α incompatibility type that shares homology with plasmids of pC-F-164_A-OXA140, pE-T654-NDM-5, p_dm760b_NDM-5, and p_dmcr749c_NDM-5. The conjugation experiment demonstrated that pST3606-2 was successfully transferred to the Escherichia coli recipient C600 with four modules of OriTfinder. Conclusion Plasmid-mediated horizontal transfer plays an important role in bla NDM-5 and bla CTX-M-261 dissemination, which increases the threat to public health due to the resistance to most β-lactam antibiotics. This is the first report of bla CTX-M-261 and bla NDM-5 in S. 1,4,[5], 12: i: -. The work provides insights into the enzymatic function and demonstrates the ongoing evolution of CTX-M enzymes and confirms urgency to control resistance of S . 1,4,[5], 12: i: -.

A sensitive and versatile electrochemical sensor based on hybridization chain reaction and CRISPR/Cas12a system for antibiotic detection - Xuemei Zhang; Li Zhu; Li Yang; Guoyu Liu; Shan Qiu; Xiaoli Xiong; Ke Huang; Ting Xiao; Liping Zhu (Analytica Chimica Acta, 2024)

Two new monoterpene esters from Illigera paviflora Dunn roots - Meng-Yuan Jiang; Xiao-Yun Pu; Wen-Ting Li; Juan Liu; Xiao-Li Zeng; Hong-Rui Li; Xi-Shan Bai; Lin Hu; Xiang-Zhong Huang (Natural Product Research, 2024)

Viologen-based ionic conjugated mesoporous polymer as the electron conveyer for efficient polysulfide trapping and conversion - Hai-Yang Li; Zhong-Shan Li; Gang-Hao Qiu; Rou-Rou Zhang; Ya-Rui Wang; Feng Wang; Ren-Wu Huang; Xiao-Fei Liu; Shuang-Quan Zang (Science Bulletin, 2024)

Efficient removal of ammonia nitrogen via a coupled system of Ni1Cu0.2-Se-T/CP anode and copper foam cathode - Luanqi Zhou; Bing Li; Hailong Wang; Qiming Li; Shan Huang; Dingchang Li; Sulin Xiang; Meng Zhang; Huimin Zhang (Journal of Environmental Chemical Engineering, 2024)

Phthalate drives splenic inflammatory response via activating HSP60/TLR4/NLRP3 signaling axis-dependent pyroptosis - Xin-Ran Ge; Yi Zhao; Hao-Ran Ren; Fu-Wei Jiang; Shuo Liu; Ming Lou; Yi-Feng Huang; Ming-Shan Chen; Jia-Xin Wang; Jin-Long Li (Environmental Pollution, 2024)

Controlled assembly of novel Fe2O3/MgFe2O4 nanotubular array structures for rapid detection of dibutylamine - Baosheng Li; Junchao Yang; Guanyi Zhang; Ming Zheng; Rui Li; Yubao Kan; Jiahui Li; Tingting Wang; Qibin Huang; Xianfa Zhang; Lihua Huo; Shan Gao; et al. (Chemical Engineering Journal, 2024)

Facile manganese ion-coordination assembly of nanogels for synergistic cancer chemo–chemodynamic-immunotherapy - Xiaonan Zhu; Qing He; Shan He; Xiaona Li; Xiaofei Huang; Junxia Wang; Xinhua Wei (Chemical Engineering Journal, 2024)

Estimations of potential evapotranspiration from CMIP6 multi-model ensemble over Africa - Ibrahim Yahaya; Zhenjie Li; Jian Zhou; Shan Jiang; Buda Su; Jinlong Huang; Runhong Xu; Peni Hausia Havea; Tong Jiang (Atmospheric Research, 2024)

Classic Famous Prescription Kai-Xin-San Ameliorates Alzheimer’s Disease via the Wnt/β-Catenin Signaling Pathway - Xiaoxiao Shan; Shujie Lv; Peng Huang; Wei Zhang; Chuanshan Jin; Yuanxu Liu; Yangyang Li; Yong Jia; Xiaoqin Chu; Can Peng; Caiyun Zhang (Molecular Neurobiology, 2024)

Insights into the molecular mechanisms underlying the different heat tolerance of the scleractinian coral Pavona decussata - Man Zhang; Shan Huang; Li Luo; Xiaopeng Yu; Hao Wang; Kefu Yu; Shengping Zhong (Coral Reefs, 2024)

Function of hormone signaling in regulating nitrogen-use efficiency in plants - Yunzhi Huang; Zhe Ji; Siyu Zhang; Shan Li (Journal of Plant Physiology, 2024)

Pigmentiphaga kullae CHJ604 improved the growth of tobacco by degrading allelochemicals and xenobiotics in continuous cropping obstacles - Jia-Xi Xiong; Ling-Shan Du; Na-Na Li; Xiu-Ting Wu; Yang Xiang; Sha Li; Lei Zou; Dongqi Liu; Duo Huang; Ze Feng Xie; Ying Wang; Jinhua Li; et al. (Journal of Hazardous Materials, 2024)

First insights into the bioaccumulation, biotransformation and trophic transfer of typical tetrabromobisphenol A (TBBPA) analogues along a simulated aquatic food chain - Chuan-Sheng Sun; Sheng-Wu Yuan; Rui Hou; Si-Qi Zhang; Qian-Yi Huang; Lang Lin; Heng-Xiang Li; Shan Liu; Yuan-Yue Cheng; Zhi-Hua Li; Xiang-Rong Xu (Journal of Hazardous Materials, 2024)

Novel insights into aerobic 17β-estradiol degradation by enriched microbial communities from mangrove sediments - Shan Zhang; Xueying Ye; Xianbin Lin; Xiangwei Zeng; Shanshan Meng; Wenqi Luo; Fei Yu; Tao Peng; Tongwang Huang; Jin Li; Zhong Hu (Journal of Hazardous Materials, 2024)

New insight into the bioaccumulation and trophic transfer of free and conjugated antibiotics in an estuarine food web based on multimedia fate and model simulation - Nian-Nian Wu; Shan Liu; Ru Xu; Qian-Yi Huang; Yun-Feng Pan; Heng-Xiang Li; Lang Lin; Rui Hou; Yuan-Yue Cheng; Xiang-Rong Xu (Journal of Hazardous Materials, 2024)

Characterization of type II IFNs and their receptors in a cyprinid fish, the blunt snout bream Megalobrama amblycephala - Bo Li; Shan Nan Chen; Lin Huang; Li Li; Li Ren; Jing Hou; Jing Yun Tian; Lan Hao Liu; P. Nie (Fish & Shellfish Immunology, 2024)

Retraction Note: MEK/ERK pathway activation by insulin receptor isoform alteration is associated with the abnormal proliferation and differentiation of intestinal epithelial cells in diabetic mice - Hui Ouyang; Hong-Sheng Yang; Tao Yu; Ti-Dong Shan; Jie-Yao Li; Can-Ze Huang; Wa Zhong; Zhong-Sheng Xia; Qi-Kui Chen (Molecular and Cellular Biochemistry, 2024)

Linking soil fertility, enzyme activity, and flavonoid-related enzymes to growth and quality of Tetrastigma hemsleyanum Diels et Gilg amended with pyrogenic organic matter and organic fertilizer - Lingtai Jiang; Shaobo Zhang; Shouzan Liu; Dongjie Geng; Mengmeng Li; Jingqing Xia; Yiwen Gu; Canchan Huang; Shan Li; Hongzhen Wang; Bai Yan (Journal of Soils and Sediments, 2024)

Associations between metal(loid) exposure with overweight and obesity and abdominal obesity in the general population: A cross-sectional study in China - Tianran Shen; Liling Zhong; Guiyuan Ji; Baolan Chen; Mengfan Liao; Lvrong Li; Huiming Huang; Jiajie Li; Yuan Wei; Shan Wu; Zihui Chen; Wenjun Ma; et al. (Chemosphere, 2024)

Diisoprenyl-cyclohexene-type meroterpenoids from a mangrove endophytic fungus Aspergillus sp. GXNU-Y65 and their anti-nonalcoholic steatohepatitis activity in AML12 cells - Feng Qin; Li Luo; Yu-Chen Liu; Xiang-Long Bo; Fu-Rong Wu; Fan-Fan Wang; Mei-Jing Tan; You-Quan Wei; Xiao-Bing Dou; Cai Yi Wang; Xi-Shan Huang; Heng-Shan Wang (Phytochemistry, 2024)

Preparation and properties of geopolymer containing phosphoric acid-activated fly ash and mechanically-milled kaolinite: Experiments and density function theory - Jiang-shan Li; Wei Zhang; Lei Lang; Chen-xi Dong; Kang Huang (Journal of Cleaner Production, 2024)

In situ formation of a covalent organic framework on g-C3N4 encapsulated with nanocellulosic carbon for enhanced photocatalytic N2-to-NH3 conversion - Tianshang Shan; Hao Luo; Shengye Wu; Jiashu Li; Fengshan Zhang; He Xiao; Liulian Huang; Lihui Chen (Fuel, 2024)

Constructing mesoporous biochar derived from waste carton: Improving multi-site adsorption of dye wastewater and investigating mechanism - Yan-Shan Wang; Tong-Rong Huo; Yan Wang; Jia-Wen Bai; Ping-Ping Huang; Chen Li; Shi-Yu Deng; Hong Mei; Jun Qian; Xiao-Chi Zhang; Chen Ding; Qiu-Yu Zhang; et al. (Environmental Research, 2024)

Biogas upgrading by biotrickling filter: Effects of temperature and packing materials - Jie-Hua Huang; Xiao-Lei Fan; Rui Li; Meng-Ting Sun; Hua Zou; Yi-Feng Zhang; Rong-Bo Guo; Shan-Fei Fu (Chemical Engineering Journal, 2024)

Cycloaspeptide H, a cyclopentapeptide from the endophytic fungus Penicillium virgatum - Ben-Chao Li; Liu-Xia Lv; Li-Li Huang; Jia-Tong Zhou; Xi-Shan Huang; Jun Li; Rui-Yun Yang; Wei-Feng Xu (Natural Product Research, 2024)

Oncogenic and immunological roles of RACGAP1 in pan-cancer and its potential value in nasopharyngeal carcinoma - Cheng-shan Zheng; Wei-mei Huang; Hong-mei Xia; Jing-lin Mi; Yuan-qing Li; Hui-qing Liang; Li Zhou; Zhou-xue Lu; Fang Wu (Apoptosis, 2024)

High-density lipoprotein cholesterol is associated with lowered cognitive recovery among acute ischemic stroke patients with mild cognitive impairment - Rui Wang; Zhuomin Jiao; Anxin Wang; Yijun Zhang; Xiangxiang Hong; Shan Huang; Jin Fu; Yinglian Zhou; Yifei Wang; Chunyang Li; Yue Liu; Ke Wei; et al. (Acta Neurologica Belgica, 2024)

Steroid metabolites as overlooked emerging contaminants: Insights from multimedia partitioning and source–sink simulation in an estuarine environment - Ru Xu; Shan Liu; Yun-Feng Pan; Nian-Nian Wu; Qian-Yi Huang; Heng-Xiang Li; Lang Lin; Rui Hou; Xiang-Rong Xu; Yuan-Yue Cheng (Journal of Hazardous Materials, 2024)

Enhanced performance of biochar-biosensor applied to heavy metals detection in constructed wetlands and biological mechanisms - Ke Zhang; Huiling Cao; Yangxingyue Li; Sujie Shan; Jia Chen; Hongbing Luo; Wei Chen; Xianbin Huang (Journal of Cleaner Production, 2024)

Fabrication of nanocomplexes for anthocyanins delivery by ovalbumin and differently dense sulphate half-ester polysaccharides nanocarriers: Enhanced stability, bio-accessibility, and antioxidant properties - Ruihong Dong; Ziyan Huang; Wenjie Ma; Qiang Yu; Jianhua Xie; Jinlong Tian; Bin Li; Jialuo Shan; Yi Chen (Food Chemistry, 2024)

Ultrasonic preparation of citral/hydroxypropyl-β-cyclodextrin inclusion complex: Application as a potential antifungal preservative in strawberry storage - Dan Shen; Xia Chang; Liling Zhou; Dandan Hao; Zhongxiang Fang; Yang Shan; Lvhong Huang; Gaoyang Li (Food Control, 2024)

Urban green, blue spaces and their joint effect are associated with lower risk of emotional and behavior problem in children and adolescents, a large population-based study in Guangzhou, China - Jing-hong Liang; Ru-yu Yang; Mei-ling Liu; Ying-qi Pu; Wen-wen Bao; Yu Zhao; Li-xin Hu; Yu-shan Zhang; Shan Huang; Nan Jiang; Xue-ya Pu; Shao-yi Huang; et al. (Environmental Research, 2024)

High-performance lithium metal batteries enabled by a nano-sized garnet solid-state electrolyte modified separator - Kai Yu; Huipeng Zeng; Jun Ma; Yidong Jiang; Huiyun Li; Ludan Zhang; Qiangqiang Zhang; Xuyi Shan; Tingting Li; Xiaoqi Wu; Hongli Xu; Wei Huang; et al. (Chemical Engineering Journal, 2024)

Elucidating influences of defects and thermal treatments on CO2 capture of a Zr-based metal–organic framework - Shan He; Ling-Xiao Li; Li-Tian Zhang; Shanshan Zeng; Chunmei Feng; Xiao-Xian Chen; Hao-Long Zhou; Xiao-Chun Huang (Chemical Engineering Journal, 2024)

The impact of climate change and human activities on the change in the net primary productivity of vegetation—taking Sichuan Province as an example - Tangrui Dai; Xiaoai Dai; Heng Lu; Tao He; Weile Li; Cheng Li; Shengqi Huang; Yiyang Huang; Chenbo Tong; Ge Qu; Yunfeng Shan; Shuneng Liang; et al. (Environmental Science and Pollution Research, 2023)

Enzymatic molecular modification of water-soluble polyphenols: Synthesis, structure, bioactivity and application - Shan Wang; Yue Li; Chaoyang Ma; Dejian Huang; Shangwei Chen; Song Zhu; Hongxin Wang (Critical Reviews in Food Science and Nutrition, 2023)

CD4 is an important host factor for Japanese encephalitis virus entry and replication in PK-15 cells - Qi Wang; Shuqing Yang; Ke Yang; Xinran Li; Yu Dai; Yi Zheng; Sanjie Cao; Qigui Yan; Xiaobo Huang; Yiping Wen; Qin Zhao; Senyan Du; et al. (Veterinary Microbiology, 2023)

The co-regulation of the gut microbiome and host genes might play essential roles in metformin gastrointestinal intolerance - Huixiang Zhang; Jiao Lai; Lihuan Zhang; Wei Zhang; Xun Liu; Qilin Gong; Hongxi Tian; Mingzhi Yang; Tao Yang; Rui Zhao; Dongqing Li; Hehua Huang; et al. (Toxicology and Applied Pharmacology, 2023)

Effect of microplastics on the adherence of coexisting background organic contaminants to natural organic matter in water - Ying Chen; Hangzhe Li; Yue Yin; Sujie Shan; Tinglin Huang; Huan Tang (Science of The Total Environment, 2023)

Occurrence and distribution of PPCPs in water from two largest urban lakes of China: First perspective from DGT in-situ measurement - Jiapei Yi; Xi Huang; Jie Hou; Junwu Xiong; Zhe Qian; Shan Liu; Jiaquan Zhang; Dacong Yin; Junyi Li; Qiuke Su; Shihua Qi; Wei Chen (Science of The Total Environment, 2023)

Synthesis of Na-A zeolite loaded bentonite and its application for removal of Cu(II) from aqueous solutions - Xiao Huang; Lei Lang; Jiang-shan Li; Chi Sun Poon (Journal of Water Process Engineering, 2023)

Organic pollutants removal from aqueous solutions using metal-organic frameworks (MOFs) as adsorbents: A review - Lixin Li; Jiazhen Han; Xiaohui Huang; Shan Qiu; Xihan Liu; Lilai Liu; Mengjie Zhao; Jiwei Qu; Jinlong Zou; Jun Zhang (Journal of Environmental Chemical Engineering, 2023)

Boosting H2O2 production over carboxymethyl cellulose modified g-C3N4 via hydrogen-bonding-assisted charge transfer - Tianshang Shan; Jiashu Li; Shengye Wu; Hui Wu; Fengshan Zhang; Guangfu Liao; He Xiao; Liulian Huang; Lihui Chen (Chemical Engineering Journal, 2023)

Refining the d-band center of S-scheme CdIn2S4/MnZnFe2O4 heterostructures by interfacial electric field with boosting photocatalytic performance - Xin Tao; Jingyu Ren; Danjun Wang; Hua Huang; Yani Li; Di Guo; Baoqin Shan; Yu Liu; Jian Wang; Yanzhong Zhen; Zhirui Niu (Chemical Engineering Journal, 2023)

A strategy to prepare low-temperature curable photosensitive polyimide with good comprehensive performance - Shan Huang; Xialei Lv; Xingwang Lai; Jinhui Li; Yao Zhang; Siyao Qiu; Guoping Zhang; Rong Sun (Chemical Engineering Journal, 2023)

Genome-Wide Identification and Expression Profiling of the FORMIN Gene Family Implies Their Potential Functions in Abiotic Stress Tolerance in Rice (Oryza sativa) - Bin Li; Zhiye Du; Nan Jiang; Shan He; Yang Shi; Kai Xiao; Lijia Xu; Kaishun Wang; Xin Wang; Longying Wu; Ji Chen; Jin Huang (Plant Molecular Biology Reporter, 2023)

Three new Clavulina species from Baiyun Mountain, Guangzhou, China - Xiao-Xia Huang; Yi-Xin Chen; Zhi-Jun Lin; Ying-Shan Liang; Li-Hong Qiu (Mycological Progress, 2023)

Genetic variation and population genetic structure of Zanthoxylum armatum in China - Shan Yan; Jingke Zhao; Xin Li; Chufeng Zhao; Dengyan Huang; Zhongli Hu; Ying Diao (Genetic Resources and Crop Evolution, 2023)

Discovery of Michael reaction acceptors from the leaves of Ailanthus altissima by a modified tactic - Zhi-Kang Duan; Shan-Shan Guo; Li Ye; Zhi-Heng Gao; Dai Liu; Guo-Dong Yao; Shao-Jiang Song; Xiao-Xiao Huang (Phytochemistry, 2023)

Light calcium isotope anomaly observed in continental basaltic lavas: A mixed signal of recycled carbonate and fractionation during melting - Yang Wang; Xunan Meng; Yongsheng He; Jian Huang; Wen-Ning Lu; Qingshang Shi; Shan Ke; Yan-Jie Tang; Shichun Huang; Shuguang Li (Lithos, 2023)

Fouling mechanism and effective cleaning strategies for vacuum membrane distillation in brackish water treatment - Shan Wang; Yongjun You; Xingpeng Wang; Weixiong Huang; Libing Zheng; Fayong Li (Desalination, 2023)

Fundicoccus culcitae sp. nov., a novel potential bacteriocin producing bacterium isolated from a spoiled eye mask - Gang Zhou; Lei Gao; Bao-Zhu Fang; Ying-Si Wang; Hong-Bing Tao; Xia Wen; Qian Wang; Xiao-Mo Huang; Qing-Shan Shi; Wen-Jun Li; Xiao-Bao Xie (Antonie van Leeuwenhoek, 2023)

Synergistic impact of co-exposures to whole blood metals on chronic kidney disease in general US adults: a cross‑sectional study of the National Health and Nutrition Examination Survey 2011–2020 - Jing-hong Liang; Ying-qi Pu; Mei-ling Liu; Wen-wen Bao; Yu-shan Zhang; Li-xin Hu; Shan Huang; Nan Jiang; Shao-yi Huang; Xue-ya Pu; Guang-hui Dong; Ya-jun Chen (Environmental Science and Pollution Research, 2023)

Association between long-term exposure to low level air pollutants and incident end-stage kidney disease in the UK Biobank: A prospective cohort - Jing Li; Liang Dai; Xiaowei Deng; Jingwen Zhang; Congying Song; Junjie Xu; Anxin Wang; Zuying Xiong; Ying Shan; Xiaoyan Huang (Chemosphere, 2023)

Associating phthalate exposure during pregnancy with preschooler's FMI, ABSI and BRI trajectories via putative mechanism pathways - Hui Gao; Yi Zhang; Li-wen Chen; Hong Gan; Meng-juan Lu; Binbin Huang; Juan Tong; Meng-long Geng; Kun Huang; Cheng Zhang; Bei-bei Zhu; Shan-shan Shao; et al. (Chemosphere, 2023)

Fe2O3 micron particles are critical for electron transfer and the distribution of electrochemically active bacteria in soil MFCs - Jingran Zhang; Shan Huang; Yongguang Yin; Liuqing Yang; Xianning Li; Wentao Jiao; Takashi Sakamaki (Science of The Total Environment, 2023)

Triterpenoid saponins from Psammosilene tunicoides and their antinociceptive activities - Yan-Hong Li; Xi-Shan Bai; Xiu-Xia Yang; Yu-Xiao Li; Hong-Rui Li; Zi-Liang Wang; Wei Wang; Kai Tian; Xiang-Zhong Huang (Phytochemistry, 2023)

Assessing the suitability of municipal sewage sludge and coconut bran as breeding medium for Oryza sativa L. seedlings and developing a standardized substrate - Linyi Lin; Jiemin Qin; Yu Zhang; Jiaxin Yin; Genmao Guo; Muhammad Amjad Khan; Yin Liu; Quan Liu; Qingqing Wang; Kenlin Chang; Ondřej Mašek; Junfeng Wang; et al. (Journal of Environmental Management, 2023)

Influences of humic acids released during sludge thermal hydrolysis on anaerobic digestion: New insights from enzymatic perspectives - Fang Huang; Hongbo Liu; Jiaxin Wen; Shan Huang; Zhiyong Zheng; Xuedong Zhang; Bo Fu; Yajie Li; Aijie Wang; He Liu (Chemical Engineering Journal, 2023)

Unraveling the cation adsorption of geopolymer binder: A molecular dynamics study - Wei Zhang; Jiang-shan Li; Xiao Huang; Zhen Chen; Lei Lang; Kang Huang (Chemosphere, 2023)

Sources, size-resolved deposition in the human respiratory tract and health risks of submicron black carbon in urban atmosphere in Pearl River Delta, China - Yuan Liu; Lina Wu; Shan Huang; Qicong Song; Weiwei Hu; Wei Chen; Zhijun Wu; Ruiqi Man; Yao He; Wei Li; Yuwen Peng; Junwen Liu; et al. (Science of The Total Environment, 2023)

RIN enhances plant disease resistance via root exudate-mediated assembly of disease-suppressive rhizosphere microbiota - Keming Yang; Ruixin Fu; Haichao Feng; Gaofei Jiang; Omri Finkel; Tianyu Sun; Mingchun Liu; Baowen Huang; Shan Li; Xiaofang Wang; Tianjie Yang; Yikui Wang; et al. (Molecular Plant, 2023)

An efficient LSTM network for predicting the tailing and multi-peaked breakthrough curves - Jie Niu; Shan Li; Wei Xu; Feifei Dong; Fen Huang; Han Qiu (Journal of Hydrology, 2023)

Efficient immobilization and detoxification of gaseous elemental mercury by nanoflower/rod WSe2/halloysite composite: Performance and mechanisms - Xuelei Duan; Yuan Li; Changxian Zhao; Yiwen Shen; Qi Guo; Zhihao Huang; Dexu Shan; Yue Gao; Kegang Zhang; Jianbo Shi; Jingfu Liu; Yongsheng Chen; et al. (Journal of Hazardous Materials, 2023)

Experimental investigation of the seismic resistance of RC beam–column connections after freeze–thaw cycle treatment - Xian-Liang Rong; Lei Li; Wei-Yuan Huang; Li-Guo Dong; Shan-Suo Zheng; Feng Wang; Dong Lu; Jun-Yan Wang (Engineering Structures, 2023)

Ferrocene-conjugated polymeric platform via amide bond formation facilitates enhanced in situ fenton reaction and robust immune responses in combination with toll-like receptor 7/8 agonist - Yanyun Hao; Hui Li; Fangfang Ren; Ruihua Feng; Yang Liu; Xia Li; Hongfei Chen; Jing Zou; Lingling Huang; Shiying Zhang; Gang Shan; Zhijie Yang; et al. (Chemical Engineering Journal, 2023)

Plant facilitation improves carbon production efficiency while reducing nitrogen input in semiarid agroecosystem - Wei Wang; Meng-Ying Li; Shuang-Guo Zhu; Aziz Khan; Xiu-Ping Tao; Guang-Fu Huang; Hai-Ying Liu; Wei Zhang; Hong-Yan Tao; Dong-Shan Gong; Chao Song; You-Cai Xiong (CATENA, 2023)

Serum lipids concentration on prognosis of high-grade glioma - Fei Huang; Shan Li; Xuezhen Wang; Caihong Wang; Xiaoxian Pan; Xiuying Chen; Weijian Zhang; Jinsheng Hong (Cancer Causes & Control, 2023)

High fat diet induces brain injury and neuronal apoptosis via down-regulating 3-β hydroxycholesterol 24 reductase (DHCR24) - Ziyin Lu; Haozhen Wang; Xiujin Zhang; Xiuting Huang; Shan Jiang; Yang Li; Ting Liu; Xiuli Lu; Bing Gao (Cell and Tissue Research, 2023)

Highly sensitive detection of microRNA-21 by nitrogen-doped carbon dots-based ratio fluorescent probe via nuclease-assisted rolling circle amplification strategy - Shan Huang; Bo Li; Pingping Mu; Wenqian Zhang; Yi Liu; Qi Xiao (Analytica Chimica Acta, 2023)

Seismogenic structure of the 2020 Jiashi, Xinjiang Ms 5.4 and Ms 6.4 moderate earthquakes - Shan-Shan Liang; Guang-Wei Zhang; Xiao-Ning Huang; Li-Ye Zou; Yan-Qiong Liu; Yun-Da Ji (Applied Geophysics, 2023)

Effects of different modifying agents on the preparation and properties of coagulants derived from excess sludge - Xueying Li; Sujie Shan; Hui Liang; Boling Li; Dapeng Li; Yong Huang (Environmental Science and Pollution Research, 2023)

Associations between multiple metals during early pregnancy and gestational diabetes mellitus under four statistical models - Luyi Li; Jialin Xu; Wenlou Zhang; Zhaokun Wang; Shan Liu; Lei Jin; Qi Wang; Shaowei Wu; Xuejun Shang; Xinbiao Guo; Qingyu Huang; Furong Deng (Environmental Science and Pollution Research, 2023)

Joint effect of whole blood metals exposure with dyslipidemia in representative US adults in NHANES 2011–2020 - Jing-hong Liang; Ying-qi Pu; Mei-ling Liu; Li-xin Hu; Wen-wen Bao; Yu-shan Zhang; Aerziguli Kakaer; Yu Zhao; Yi-can Chen; Xue-ya Pu; Shao-yi Huang; Nan Jiang; et al. (Environmental Science and Pollution Research, 2023)

Geochemical behaviors of uranium and thorium during weathering and pedogenesis of carbonate rock: constraint from their speciation - Qiang Ma; Bing-jie Zhou; Zhi-gang Feng; Xiao-long Wang; Rong Chen; Pei-shan Li; Chong Huang (Environmental Science and Pollution Research, 2023)

Preparation of cationic aggregates derived from sewage sludge for efficient capture of organic matter - Hui Liang; Sujie Shan; Xueying Li; Dapeng Li; Yong Huang (Chemosphere, 2023)

Buffering capacity of submerged macrophytes against nutrient pulses increase with its coverage in shallow lakes - Chaochao Lv; Yuqing Tian; Liangliang Huang; Hang Shan; Qingchuan Chou; Wei Zhang; Haojie Su; Kuanyi Li; Xiaolin Zhang; Leyi Ni; Te Cao; Erik Jeppesen (Chemosphere, 2023)

Efficient ammonia removal promoted in a bifunctional system constructed with NiCu–S/DSA electrodes - Huimin Zhang; Xing Tong; Hailong Wang; Luanqi Zhou; Shan Huang; Dingchang Li; Yifei Wang; Huoqing Xiao; Meng Zhang (Journal of Cleaner Production, 2023)

Proteins from different sources in a high-fat food matrix influence lipid hydrolysis through bolus coalescence and interactions with bile salts - Mengzhen Ding; Zixin Huang; Zhiji Huang; Zerun Zhao; Di Zhao; Kai Shan; Weixin Ke; Miao Zhang; Guanghong Zhou; Chunbao Li (Food Hydrocolloids, 2023)

Oxytetracycline-induced oxidative liver damage by disturbed mitochondrial dynamics and impaired enzyme antioxidants in largemouth bass (Micropterus salmoides) - Tong Li; Min Jin; Lishi Huang; Yupeng Zhang; Jiali Zong; Hongying Shan; Hao Kang; Man Xu; Haifeng Liu; Ye Zhao; Quanquan Cao; Jun Jiang (Aquatic Toxicology, 2023)

Low-carbon development pathways for resource-based cities in China under the carbon peaking and carbon neutrality goals - Kejun Li; Ya Zhou; Xuanhao Huang; Huijuan Xiao; Yuli Shan (Environmental Science and Pollution Research, 2023)

Monitoring H2S fluctuation during autophagic fusion of lysosomes and mitochondria using a lysosome-targeting fluorogenic probe - Taoyun Wang; Xu Huang; Sheng Yang; Shan Hu; Xianglan Zheng; Guojiang Mao; Yi Li; Yibo Zhou (Analytica Chimica Acta, 2023)

Early Cretaceous Ningguo-Guangde weakly fractionated I-type granitoids, Jiangnan tungsten belt, China: Implications for petrogenesis and W Mo mineralization - Xin Zhang; Jiancheng Xie; Shan Huang; Likai Ge; Quanzhong Li; Jianmin Liu; Jun Yan (Journal of Geochemical Exploration, 2023)

Comparative Physiological and Transcriptomic Analysis Provide New Insights of Crucial Pathways and Genes Regulating Kenaf Salt Tolerance - Yali Hu; Zengqiang Li; Meiqiong Tang; Dengjie Luo; Muhammad Haneef Kashif; Shan Cao; Caijin Wang; Jiao Yue; Zhen Huang; Jiao Pan; Xia Wu; Qijing Wu; et al. (Journal of Plant Growth Regulation, 2023)

RETRACTED ARTICLE: Vacuolar protein sorting 35 (VPS35) acts as a tumor promoter via facilitating cell cycle progression in pancreatic ductal adenocarcinoma - Yanzhi Gai; Liheng Qian; Shuheng Jiang; Jun Li; Xueli Zhang; Xiaomei Yang; Hong Pan; Yingna Liao; Huiling Wang; Shan Huang; Shan Zhang; Huizhen Nie; et al. (Functional & Integrative Genomics, 2023)

Incidence and Risk Factors for Dysphagia Following Cerebellar Stroke: a Retrospective Cohort Study - Li Huang; Yunlu Wang; Jikang Sun; Lequn Zhu; Jimin Liu; Yuwei Wu; Chunlei Shan; Juntao Yan; Ping Wan (The Cerebellum, 2023)
The cerebellum is known to play a supportive role in swallowing-related functions; however, wide discrepancies about the incidence rate of swallowing disorders following cerebellar strokes exist within the literature. This study aimed to investigate the incidence rate of dysphagia and the factors which may affect the presence of dysphagia and clinical recovery in individuals diagnosed with cerebellar stroke. A retrospective chart audit of 1651 post-stroke patients (1049 males and 602 females) admitted with a cerebellar stroke to a comprehensive tertiary hospital in China was conducted. Data on demographics, medical, along with swallowing function assessment were collected. Differences between dysphagic and non-dysphagic groups were evaluated using t -tests and Pearson’s chi-square test. Univariate logistic regression analysis was performed to establish factors associated with the presence of dysphagia. A total of 11.45% of participants were identified with dysphagia during inpatient admission. Individuals with mixed types of stroke, multiple lesions in the cerebellum, and ages older than 85 years old were more likely to develop dysphagia. Moreover, the prognosis of dysphagia following a cerebellar stroke was associated with lesions in different parts of the cerebellum. The cumulative recovery rates from the best to worse were the right hemisphere group, the cerebellum vermis or peduncle group, and both the hemisphere group and the left hemisphere group, respectively.

Free and conjugated forms of metabolites are indispensable components of steroids: The first evidence from an estuarine food web - Shan Liu; Ru Xu; Yun-Feng Pan; Qian-Yi Huang; Nian-Nian Wu; Heng-Xiang Li; Lang Lin; Rui Hou; Xiang-Rong Xu (Water Research, 2023)

Discovery of uncommon terpenoids from the South China Sea soft coral Sinularia scabra - Kui Wang; Jing Liu; Jian Huang; Xue Leng; Te Li; Han Ouyang; Wenhan Lin; Xia Yan; Shan He (Phytochemistry, 2023)

Photolysis frequency of nitrophenols derived from ambient measurements - Yuwen Peng; Bin Yuan; Suxia Yang; Sihang Wang; Xiaoyun Yang; Wenjie Wang; Jin Li; Xin Song; Caihong Wu; Jipeng Qi; E. Zheng; Chenshuo Ye; et al. (Science of The Total Environment, 2023)

Modeling nutrient flows from land to rivers and seas – A review and synthesis - Xiaoyang Shan; Zhiqiang Zhu; Jiyong Ma; Dinghui Fu; Yanwei Song; Qipei Li; Zanhui Huang; Lixin Pei; Hongwei Zhao (Marine Environmental Research, 2023)

Manganese and copper additions differently reduced cadmium uptake and accumulation in dwarf Polish wheat (Triticum polonicum L.) - Xing Chen; Shan Yang; Jian Ma; Yiwen Huang; Yi Wang; Jian Zeng; Jun Li; Siyu Li; Dan Long; Xue Xiao; Lina Sha; Dandan Wu; et al. (Journal of Hazardous Materials, 2023)

Differential therapeutic activity of a cargo-free nanoparticle in eosinophilic and neutrophilic asthma mouse models - Xiali Liu; Huasheng Zhang; Huiqiang Ma; Jiameng Gong; Kaifeng Huang; Lu Wang; Yuting Ji; Liya Sun; Xiaoyu Wang; Li Li; Lei Shen; Shan-Yu Fung; et al. (Chemical Engineering Journal, 2023)

Inhibition of ferroptosis by icariin treatment attenuates excessive ethanol consumption-induced atrial remodeling and susceptibility to atrial fibrillation, role of SIRT1 - Li-Ming Yu; Xue Dong; Tao Huang; Ji-Kai Zhao; Zi-Jun Zhou; Yu-Ting Huang; Yin-Li Xu; Qiu-Sheng Zhao; Zhi-Shang Wang; Hui Jiang; Zong-Tao Yin; Hui-Shan Wang (Apoptosis, 2023)

Hydrological properties of biochar-amended expansive soil under dynamic water environment and biochar-amended soil’s application in green roofs - Muyang Li; Ankit Garg; Shan Huang; Mingjie Jiang; Guoxiong Mei; Jiaqin Liu; Hao Wang (Acta Geophysica, 2023)

Pharmacokinetics and residue elimination of metalaxyl enantiomers in snakehead (Channa argus) - Hao Zhou; Meiyu Zhang; Qi Shan; Heqing Huang; Meiling Zhang; Shugui Liu; Jiawei Lin; Lisha Ma; Guangming Zheng; Lichun Li; Cheng Zhao; Xiaoxin Dai; et al. (Aquaculture, 2023)

The evolution of soil microstructure and micromineralogy along a soil age gradient on the Galápagos Islands (Ecuador) - Martin H. Gerzabek; Georges Stoops; Franz Ottner; Shan-Li Wang; Liang-Sin Huang; Franz Zehetner (Geoderma Regional, 2023)

Nigericin treatment activates endoplasmic reticulum apoptosis pathway in goldfish kidney leukocytes - Songwei Zhu; Xinyuan Yue; Kejing Huang; Xionglin Li; Moussa Gouife; Mateen Nawaz; Rongrong Ma; Jianhu Jiang; Shan Jin; Jiasong Xie (Fish & Shellfish Immunology, 2023)

Purinergic receptors mediate endothelial dysfunction and participate in atherosclerosis - Xian-Ming Wu; Ning Zhang; Jiang-Shan Li; Zhi-Hong Yang; Xiao-Lou Huang; Xiao-Fang Yang (Purinergic Signalling, 2023)
Atherosclerosis is the main pathological basis of cardiovascular disease and involves damage to vascular endothelial cells (ECs) that results in endothelial dysfunction (ED). The vascular endothelium is the key to maintaining blood vessel health and homeostasis. ED is a complex pathological process involving inflammation, shear stress, vascular tone, adhesion of leukocytes to ECs, and platelet aggregation. The activation of P2X4, P2X7, and P2Y2 receptors regulates vascular tone in response to shear stress, while activation of the A2A, P2X4, P2X7, P2Y1, P2Y2, P2Y6, and P2Y12 receptors promotes the secretion of inflammatory cytokines. Finally, P2X1, P2Y1, and P2Y12 receptor activation regulates platelet activity. These purinergic receptors mediate ED and participate in atherosclerosis. In short, P2X4, P2X7, P2Y1, and P2Y12 receptors are potential therapeutic targets for atherosclerosis.

Introduction of non‐native fish for aquaculture in China: A systematic review - Bin Kang; Jean R. S. Vitule; Shan Li; Fangmin Shuai; Liangliang Huang; Xiaoxia Huang; Jinghui Fang; Xiaotao Shi; Yugui Zhu; Dongpo Xu; Yunrong Yan; Fangrui Lou (Reviews in Aquaculture, 2023)
Aquaculture, especially of non‐native species and translocated domestic species, is a greatly encouraged way of relieving the conflicts between food and economic demand and resource depletion. We herein summarized the introduction history of non‐native fish for aquacultural use in China, including 105 species introduced from abroad and 61 species translocated domestically across river basins, which has brought great economic benefits but high ecological risks. Of these, one‐fourth have successfully established wild populations in natural waters and 15% have successfully invaded. We presented specific examples of seven aquaculture species/taxa and three aquarium species/taxa to explain their outcomes. The notable economic benefits, complex species composition and strain selection of tilapias, carps and sturgeons may together facilitate their invasion, and result in fish diversity decline, genetic pollution, and loss of ecosystem service. We specifically reviewed invasion cases in lakes and reservoirs and found that lakes in western China and reservoirs made by major hydroprojects are hotspots for non‐native species, and this has led to the disappearance of endemic species and changes to the original faunal composition. The escaped non‐native fish introduced via aquaculture has changed the original fish biogeography, resulting in the loss of assemblage uniqueness and causing faunal homogeneity. China has achieved significant progress in completing the Aichi Targets by improving the legal system and strengthening conservational actions on controlling non‐native species. Further actions, especially on risk assessment and management of non‐native species are expected for a healthy outlook for the aquaculture industry of China.

Highly efficient activation of sulfite by surface oxidized pyrite for atrazine degradation: Experimental and DFT study - Min Tao; Jian Zhang; Jiliang Lv; Jiaquan Zhang; Yuxiao Li; Shan Liu; Wensheng Xiao; Ying Huang; Han Zheng (Journal of Environmental Chemical Engineering, 2023)

Granitic record of the assembly of the Asian continent - Tao Wang; Ying Tong; He Huang; Hongrui Zhang; Lei Guo; Zhengxiang Li; Xiaoxia Wang; Bruce Eglington; Shan Li; Jianjun Zhang; Tatiana V. Donskaya; Oleg Petrov; et al. (Earth-Science Reviews, 2023)

DNAzymes-conjugated upconversion nanoamplicon for in-situ ultrasensitive detection and imaging of microRNA in vivo - Yi Zhang; Da Luo; Yin Zhang; Qi-Hai Zhang; Qing-Yuan Ji; Shi-Kang Zhou; Shan Huang; Li-li Li; Feng Lu; Wei-Feng Yao; Fang-Fang Cheng; Jun-Jie Zhu; et al. (Chemical Engineering Journal, 2023)

Effects and mechanism on cadmium adsorption removal by CaCl2-modified biochar from selenium-rich straw - Zongyu Gao; Dexin Shan; Jiahong He; Tao Huang; Yuan Mao; Haiping Tan; Huiting Shi; Tingzhen Li; Taiping Xie (Bioresource Technology, 2023)

Accidental acquisition of a rescued Japanese encephalitis virus with unspliced introns in the viral genome when using an intron-based stabilization approach - Ying Huang; Hongshan Xu; Shan Liu; Jiansheng Lu; Lili Jia; Yuhua Li; Rong Wang; Peng Yang; Yongxin Yu; Zhixin Yang (Archives of Virology, 2023)
The intron-based stabilization approach is a very useful strategy for construction of stable flavivirus infectious clones. SA 14 -14-2 is a highly attenuated Japanese encephalitis (JE) live vaccine strain that has been widely used in China since 1989. To develop safe and effective recombinant vaccines with SA 14 -14-2 as a backbone vector, we constructed the DNA-based infectious clone pCMW-JEV of SA 14 -14-2 using the intron-based stabilization approach and acquired the rescued virus rDJEV, which retained the biological properties of the parental virus. Unexpectedly, a rescued virus strain with altered virulence, designated rHV-DJEV, was accidentally acquired in one of the transfection experiments. rHV-DJEV showed up to 10 5 -fold increased neurovirulence compared with the SA 14 -14-2 parental strain. Genome sequencing showed that the inserted introns were still present in the genome of rHV-DJEV. Therefore, we think that the intron-based stabilization approach should be used with caution in vaccine development and direct iDNA immunization.

Sources, distribution and decomposition of soil organic matter based on an effective biomarker in the pastoral areas of Zoige Plateau, China - Bin Wang; Tingqian Shan; Junjie Wang; Fuyang Huang; Wei Liu; Weiguo Tu; Sen Li; Qingsong Chen (Chemosphere, 2023)

CO2 mineral sequestration and nickel recovery from laterite ore by using waste copperas - Yuxiang Gao; Xi Jin; Liumei Teng; Sohrab Rohani; Minyu He; Jiangling Li; Shan Ren; Qingcai Liu; Junbin Huang; Huamei Duan; Yuntao Xin; Weizao Liu (Fuel, 2023)

Complexing agents-free bioelectrochemical trickling systems for highly-efficient mesothermal NO removal: The role of extracellular polymer substances - Xingzhu Huang; Shaofeng Zhou; Jianjun Li; Xiaojun Wang; Shaobin Huang; Guoping Sun; Shan Yang; Jia Xing; Meiying Xu (Bioresource Technology, 2023)

Photocatalytic degradation of tetracycline hydrochloride by a Fe3O4/g-C3N4/rGO magnetic nanocomposite mechanism: modeling and optimization - Junyue Shan; Xianliang Wu; Caifang Li; Jiwei Hu; Zhenming Zhang; Huijuan Liu; Pinhua Xia; Xianfei Huang (Environmental Science and Pollution Research, 2023)

Effect of alkaline washing treatment on leaching behavior of municipal solid waste incineration bottom ash - Zhen Chen; Jiang-Shan Li; Dongxing Xuan; Chi Sun Poon; Xiao Huang (Environmental Science and Pollution Research, 2023)

Spatiotemporal variations of water use efficiency and its driving factors in Inner Mongolia from 2001 to 2020 - Li Mei; Siqin Tong; Shan Yin; Yuhai Bao; Xiaojun Huang; Tuya Alateng; Yongfang Wang; Enliang Guo; Zhihui Yuan; Dalai Nashun; Suriguga Gao; Xinyi Liu; et al. (Journal of Geographical Sciences, 2023)

Portable high-throughput multimodal immunoassay platform for rapid on-site COVID-19 diagnostics - Yanke Shan; Bin Wang; Huachuan Huang; Keding Yan; Wenzhi Li; Shouyu Wang; Fei Liu (Analytica Chimica Acta, 2023)

Spatially explicit model of the Cryptosporidium and Giardia disease burden from surface and ground waters in urban and rural areas of the Three Gorges Reservoir watershed in Chongqing, China - Qian Huang; Shan Huang; Bo Li; Yanhong Xiong; Weijie Kuang; Shunxin Xiao; Jianghui Yi; Feng Zhao; Guosheng Xiao (Environmental Science and Pollution Research, 2022)
Cryptosporidium and Giardia (major causes of diarrhea) are widely distributed in Chinese source waters and threaten human health. A new spatially explicit GloWPa-TGR-Crypt-Giar C1 model is presented to simultaneously estimate mean monthly (oo)cyst concentrations in surface and ground waters in the Three Gorges Reservoir (TGR) watershed. A quantitative risk assessment of protozoal infections considered different source waters, transmission pathways, regions, susceptible subpopulations, and drinking water treatments. Monthly mean Cryptosporidium oocyst and Giardia cyst concentrations ranged between 0.5–19.3 oocysts/10 L and 0.2–5.0 cysts/10 L in surface water, respectively, and 0.007–0.3 oocysts/10 L and 0.002–0. 2 cysts/10 L in groundwater. The cumulative disease burdens attributable to cryptosporidiosis and giardiasis were, respectively, 5.77×10 −5 DALYs (disability-adjusted life years/person/year) and 4.63×10 −6 DALYs in urban areas, and 6.35×10 −4 DALYs and 8.84×10 −5 DALYs in rural areas, which were much higher than the reference risk level recommended by the World Health Organization ( $${10}^{-6}$$ 10 - 6 DALYs). The annual burden associated with consuming surface water was calculated to be 3.84×10 −4 DALYs for Cryptosporidium and $$5.10× {10}^{-5}$$ 5.10 × 10 - 5 DALYs for Giardia , whereas consuming groundwater entailed the lower burdens (1.26×10 −5 and 3.50×10 −6 DALYs, respectively). Most DALYs were a consequence of consumption of directly supplied surface water. Fifty percent of the health burden was carried by immunodeficiency with HIV. Children (0–4 years) were more likely to have an individual disease burden than adults (15–64 years). Males were more susceptible than females. Improving sanitation through adequate ozone and microfiltration treatment should be considered when attempting to reduce disease burden. Sensitivity analysis highlighted the importance of reducing (oo)cyst loads to protect the watershed. The methodology and results described will help in evaluating and reducing the burden of protozoal infection associated with surface and ground waters in the TGR and similar watersheds. Graphical Abstract

Interoperable vocabulary for marine microbial flow cytometry - Melilotus Thyssen; Gérald Grégori; Véronique Créach; Soumaya Lahbib; Mathilde Dugenne; Hedy M. Aardema; Luis-Felipe Artigas; Bangqin Huang; Aude Barani; Laureen Beaugeard; Amel Bellaaj-Zouari; Alfred Beran; et al. (Frontiers in Marine Science, 2022)
The recent development of biological sensors has extended marine plankton studies from conducting laboratory bench work to in vivo and real-time observations. Flow cytometry (FCM) has shed new light on marine microorganisms since the 1980s through its single-cell approach and robust detection of the smallest cells. FCM records valuable optical properties of light scattering and fluorescence from cells passing in a single file in front of a narrow-collimated light source, recording tens of thousands of cells within a few minutes. Depending on the instrument settings, the sampling strategy, and the automation level, it resolves the spatial and temporal distribution of microbial marine prokaryotes and eukaryotes. Cells are usually classified and grouped on cytograms by experts and are still lacking standards, reducing data sharing capacities. Therefore, the need to make FCM data sets FAIR (Findability, Accessibility, Interoperability, and Reusability of digital assets) is becoming critical. In this paper, we present a consensus vocabulary for the 13 most common marine microbial groups observed with FCM using blue and red-light excitation. The authors designed a common layout on two-dimensional log-transformed cytograms reinforced by a decision tree that facilitates the characterization of groups. The proposed vocabulary aims at standardising data analysis and definitions, to promote harmonisation and comparison of data between users and instruments. This represents a much-needed step towards FAIRification of flow cytometric data collected in various marine environments.

Occurrence and damage of epidemic fungal diseases in middle and late stages of sugarcane growth in Yunnan Province of China - Wen-Feng Li; Xiao-Yan Wang; Hong-Li Shan; Rong-Yue Zhang; Yin-Hu Li; Wen-Jie Lu; Ying-Kun Huang (European Journal of Plant Pathology, 2022)

Starch, cellulose and plant extracts as green inhibitors of metal corrosion: a review - Li Huang; Wei-Qiang Chen; Shan-Shan Wang; Qing Zhao; Hui-Jing Li; Yan-Chao Wu (Environmental Chemistry Letters, 2022)

Establishment of an astrocyte‐like cell line from the brain of tilapia ( Oreochromis niloticus ) for virus pathogenesis and a vitro model of the blood–brain barrier - Yuan Li; Yu Huang; Jia Cai; Dongneng Jiang; Ji‐chang Jian; Yi‐shan Lu; Bei Wang (Journal of Fish Diseases, 2022)
A new cell line was established from the brain of a cultured fish, tilapia ( Oreochromis niloticus ), designated as TA‐02 (Tilapia Astrocyte clone 02 cell line). The TA‐02 cells are grown for 300 days in an L‐15 medium supplemented with 10% fetal bovine serum (FBS). This cell line showed excellent proliferative capacity and expressed various neuroglial cell markers, including SOX2, SOX10, Hes1, Notch1, Occludin, E‐cadherin, and GFAP. In addition, TA‐02 cells were susceptible to Tilapia Lake Virus (TiLV) as demonstrated by the presence of a severe cytopathic effect (CPE), virus particle in a transmission electron microscope (TEM), and PCR positive signal. Bacterial cytotoxicity studies showed that Streptococcus agalactiae was toxic to TA‐02 cells. When co‐culture with trans‐well, TA‐02 exhibited prominent barrier properties, manifested by tight intercellular junctions and increased trans‐endothelial electrical resistance (TEER). In addition, the barrier is effective against Escherichia coli (non‐meningitis pathogenic bacteria). In contrast, S. agalactiae (meningitis pathogenic bacteria) can pass through the membrane comprising the cells in the trans‐well insert. The newly established TA‐02 cell line provided a valuable tool for virus pathogenesis and a vitro model of the fish blood–brain barrier.

History of suicide attempts associated with the thinning right superior temporal gyrus among individuals with schizophrenia - Yi Yin; Jinghui Tong; Junchao Huang; Baopeng Tian; Song Chen; Shuping Tan; Zhiren Wang; Fude Yang; Yongsheng Tong; Fengmei Fan; Peter Kochunov; Neda Jahanshad; et al. (Brain Imaging and Behavior, 2022)

Influence of nitrogen wet deposition on nitrogen output in a typical watershed in the Three Gorges Reservoir Area - Chen-dong Lu; Liu-yi Zhang; Kun Yan; Yu-kuan Wang; Shan-gao Xiong; Chen-tao Huang; Ting-zhen Li; Mao-fei Ni (Journal of Mountain Science, 2022)

ML323, a USP1 inhibitor triggers cell cycle arrest, apoptosis and autophagy in esophageal squamous cell carcinoma cells - Yaxin Sun; Beibei Sha; Wenjing Huang; Miaomiao Li; Shan Zhao; Yuan Zhang; Jie Yan; Zheng Li; Jingwen Tang; Peiyan Duan; Jianxiang Shi; Pei Li; et al. (Apoptosis, 2022)

Variations in nutrients and microbes during the occurrence and extinction of algal blooms: A mesocosm experiment with the addition of marine aquaculture sediment - Yuanmin Sun; Kunxian Tang; Yong Ma; Xuan Zhu; Heyang Li; Fei Zhang; Shan Chen; Haiping Huang (Frontiers in Marine Science, 2022)
The release of pollutants in sediment often causes secondary pollution of seawater. In this paper, marine aquaculture sediment was added to seawater in a coastal land–based mesocosm, and the changes in microbial and physicochemical parameters were measured to study the influence of sediment disturbance on seawater. The results showed that sediment disturbance had adverse effects on seawater. After adding and stirring the aquaculture sediment, the concentration of dissolved oxygen (DO) gradually decreased, and those of nutrients gradually increased; in particular, the concentrations of ammonia and dissolved inorganic phosphorus (DIP) increased most sharply. After day 9, a bloom dominated by Chaetoceros occurred. Concentrations of chlorophyll a (Chl-a) increased, and two obvious Chl-a peaks were observed; the trends of DO and pH were similar to that of Chl-a during the bloom period; and DIP and ammonia were exhausted during periods of Chl-a peaks. During the extinction of algal blooms, the concentrations of Chl-a and DO decreased, whereas those of DIP and ammonia increased. The variation trends of bacteria and viruses were similar to that of Chl-a, with two obvious peaks, which were later than those of Chl-a. There were close connections between Chl-a and nutrients, bacteria and viruses and they showed a trend of changes in turn from nutrients to phytoplankton to bacteria to viruses during the experiment. We concluded that bloom formation was mainly affected by nutrients and weather, and the main reason for bloom decline was the depletion of nutrients. The increase in zooplankton, bacteria, and virus abundance was the ecological effect after the occurrence of algal blooms, and they affected the development of algal blooms.

Assessing economic sustainability and ecological efficiency with genuine progress indicator: a case study of the Yangtze River Delta from 2000 to 2018 - Yongjun Li; Jing Qiao; Lei Xie; Lingyan Huang; Yue Su; Mengmeng Zhou; Ke Wang; Jing Zhang; Shan He; Lu Huang (Environmental Science and Pollution Research, 2022)

Research on fish identification in tropical waters under unconstrained environment based on transfer learning - Shan Zhang; Weifang Liu; Yupeng Zhu; Wei Han; Yi Huang; Jianqiang Li (Earth Science Informatics, 2022)
Seafloor unconstrained environment video is shot in uncontrolled open sea area. There are multiple backgrounds, complex illumination and weather changes, and rapid growth of algae and attached lenses, which affect the stability of video shooting quality, resulting in difficulty in image recognition. At present, there is still no algorithm that is superior to other methods generally, and it is necessary to build a model combined with specific scenes and applications. In this paper, a fish identification method in tropical waters based on transfer learning under unconstrained environment is proposed. Firstly, the image is pre-processed by affine transformation to realize data enhancement. Furthermore, RestNet50 deep convolutional neural network is constructed based on transfer learning to compare the effect of fish recognition before and after transfer learning. The results show that, the accuracy and loss indicators are better than those of non-transfer learning when the trained model of imagenet is introduced as the initial weight of the network. When the model is trained to 150 epochs, the indicators begin to converge, which can better complete the fish identification task in tropical waters under unconstrained environment.

Graphene-based photocatalytic nanocomposites used to treat pharmaceutical and personal care product wastewater: A review - Caifang Li; Xianliang Wu; Jiwei Hu; Junyue Shan; Zhenming Zhang; Xianfei Huang; Huijuan Liu (Environmental Science and Pollution Research, 2022)

Liposome-Encapsulated Rec8 and Dmrt1 Plasmids Induce Red-Spotted Grouper (Epinephelus akaara) Testis Maturation - Xuzhuo Duan; Xianze Jia; Kaishan Liang; Fengqi Huang; Jinhong Shan; Huitao Chen; Xinhe Ruan; Lihua Li; Huihong Zhao; Qing Wang (Marine Biotechnology, 2022)

Estimation of Avian Influenza Viruses in Water Environments of Live Poultry Markets in Changsha, China, 2014 to 2018 - Xiaoyu Li; Rusheng Zhang; Zheng Huang; Dong Yao; Lei Luo; Jingfang Chen; Wen Ye; Lingzhi Li; Shan Xiao; Xiaolei Liu; Xinhua Ou; Biancheng Sun; et al. (Food and Environmental Virology, 2022)

Carbonated Big Mantle Wedge Extending to the NE Edge of the Stagnant Pacific Slab: Constraints from Late Mesozoic-Cenozoic Basalts from Far Eastern Russia - Ronghua Cai; Shan Xu; Dmitri A. Ionov; Jian Huang; Sheng-Ao Liu; Shuguang Li; Jingao Liu (Journal of Earth Science, 2022)

Handelin extends lifespan and healthspan of Caenorhabditis elegans by reducing ROS generation and improving motor function - Huijie Zhang; Jiawei Qin; Xinqiang Lan; Weirong Zeng; Jing Zhou; Tian-E Huang; Wan-Li Xiao; Qi-Quan Wang; Sujiao Sun; Weiting Su; Wenhui Nie; Shan Yang; et al. (Biogerontology, 2022)

ipa1 improves rice drought tolerance at seedling stage mainly through activating abscisic acid pathway - Menghao Zhu; Yonggang He; Mingqiang Zhu; Ayaz Ahmad; Shuang Xu; Zijun He; Shan Jiang; Jinqiu Huang; Zhihui Li; Shaojia Liu; Xin Hou; Zhihong Zhang (Plant Cell Reports, 2022)

A community effort to assess and improve computerized interpretation of 12-lead resting electrocardiogram - Zijian Ding; Guijin Wang; Huazhong Yang; Ping Zhang; Dapeng Fu; Zhen Yang; Xinkang Wang; Xia Wang; Zhourui Xia; Chiming Zhang; Wenjie Cai; Binhang Yuan; et al. (Medical & Biological Engineering & Computing, 2022)
Computerized interpretation of electrocardiogram plays an important role in daily cardiovascular healthcare. However, inaccurate interpretations lead to misdiagnoses and delay proper treatments. In this work, we built a high-quality Chinese 12-lead resting electrocardiogram dataset with 15,357 records, and called for a community effort to improve the performances of CIE through the China ECG AI Contest 2019. This dataset covers most types of ECG interpretations, including the normal type, 8 common abnormal types, and the other type which includes both uncommon abnormal and noise signals. Based on the Contest, we systematically assessed and analyzed a set of top-performing methods, most of which are deep neural networks, with both their commonalities and characteristics. This study establishes the benchmarks for computerized interpretation of 12-lead resting electrocardiogram and provides insights for the development of new methods.

A genome-wide association study reveals that the cytochrome b5 involved in seed reserve mobilization during seed germination in rice - Zhibo Huang; Jifeng Ying; Liling Peng; Shan Sun; Chengwei Huang; Can Li; Zhoufei Wang; Yongqi He (Theoretical and Applied Genetics, 2021)

Hydrological characteristics and changes in the Nu-Salween River basin revealed with model-based reconstructed data - Fan Yang; Hui Lu; Kun Yang; Guang-wei Huang; Yi-shan Li; Wei Wang; Ping Lu; Fu-qiang Tian; Yu-gang Huang (Journal of Mountain Science, 2021)

Retraction Note to: Numerical simulation of ocean sea temperature based on feature prediction and monitoring of coastal running health data - Shan Huang; Xu Li (Arabian Journal of Geosciences, 2021)

Resistance to pokkah boeng disease in new and main sugarcane varieties cultivated in China - Hongli Shan; Xiaoyan Cang; Wei Qin; Wenfeng Li; Xiaoyan Wang; Rongyue Zhang; Yingkun Huang (Euphytica, 2021)

RETRACTED ARTICLE: Numerical simulation of ocean sea temperature based on feature prediction and monitoring of coastal running health data - Shan Huang; Xu Li (Arabian Journal of Geosciences, 2021)

Evaluation of field resistance to brown stripe disease in novel and major cultivated sugarcane varieties in China - Xiao-Yan Wang; Xiao-Yan Cang; Wei Qin; Hong-Li Shan; Rong-Yue Zhang; Chang-Mi Wang; Wen-Feng Li; Ying-Kun Huang (Journal of Plant Pathology, 2021)

FABP5 Deficiency Impairs Mitochondrial Function and Aggravates Pathological Cardiac Remodeling and Dysfunction - Shanquan Gao; Guoqi Li; Yihui Shao; Zhipeng Wei; Shan Huang; Feiran Qi; Yao Jiao; Yulin Li; Congcong Zhang; Jie Du (Cardiovascular Toxicology, 2021)

Genetic Architecture of Childhood Kidney and Urological Diseases in China - Ye Fang; Hua Shi; Tianchao Xiang; Jiaojiao Liu; Jialu Liu; Xiaoshan Tang; Xiaoyan Fang; Jing Chen; Yihui Zhai; Qian Shen; Guomin Li; Li Sun; et al. (Phenomics, 2021)
Kidney disease is manifested in a wide variety of phenotypes, many of which have an important hereditary component. To delineate the genotypic and phenotypic spectrum of pediatric nephropathy, a multicenter registration system is being implemented based on the Chinese Children Genetic Kidney Disease Database (CCGKDD). In this study, all the patients with kidney and urological diseases were recruited from 2014 to 2020. Genetic analysis was conducted using exome sequencing for families with multiple affected individuals with nephropathy or clinical suspicion of a genetic kidney disease owing to early-onset or extrarenal features. The genetic diagnosis was confirmed in 883 of 2256 (39.1%) patients from 23 provinces in China. Phenotypic profiles showed that the primary diagnosis included steroid-resistant nephrotic syndrome (SRNS, 23.5%), glomerulonephritis (GN, 32.2%), congenital anomalies of the kidney and urinary tract (CAKUT, 21.2%), cystic renal disease (3.9%), renal calcinosis/stone (3.6%), tubulopathy (9.7%), and chronic kidney disease of unknown etiology (CKDu, 5.8%). The pathogenic variants of 105 monogenetic disorders were identified. Ten distinct genomic disorders were identified as pathogenic copy number variants (CNVs) in 11 patients. The diagnostic yield differed by subgroups, and was highest in those with cystic renal disease (66.3%), followed by tubulopathy (58.4%), GN (57.7%), CKDu (43.5%), SRNS (29.2%), renal calcinosis /stone (29.3%) and CAKUT (8.6%). Reverse phenotyping permitted correct identification in 40 cases with clinical reassessment and unexpected genetic conditions. We present the results of the largest cohort of children with kidney disease in China where diagnostic exome sequencing was performed. Our data demonstrate the utility of family-based exome sequencing, and indicate that the combined analysis of genotype and phenotype based on the national patient registry is pivotal to the genetic diagnosis of kidney disease.

Molecular determination of RSD and the Bru1 gene in commonly used sugarcane (Saccharum officinarum) breeding parents in China - Jie Li; Rongyue Zhang; Xiaoyan Cang; Jiayong Liu; Hongli Shan; Changmi Wang; Xiaoyan Wang; Wenjie Lu; Yingkun Huang (Euphytica, 2021)

Icaritin Inhibits Skin Fibrosis through Regulating AMPK and Wnt/β-catenin Signaling - Ming Li; Qingmei Liu; Shan He; Xiangzhen Kong; Jinpei Lin; Yan Huang; Wenyu Wu; Jinfeng Wu (Cell Biochemistry and Biophysics, 2021)

Flow depth, velocity, and sediment motions in a straight widened channel with vegetated floodplains - Fujian Li; Yuqi Shan; Sheng Huang; Chao Liu; Xingnian Liu (Environmental Fluid Mechanics, 2021)

New cytotoxic biflavones from Selaginella doederleinii - Li-Fei Liu; Hui-Hui Sun; Jian-Bing Tan; Qi Huang; Fei Cheng; Kang-Ping Xu; Zhen-Xing Zou; Gui-Shan Tan (Natural Product Research, 2021)

Essential oil from Artemisia annua aerial parts: composition and repellent activity against two storage pests - Hong Liu; Shan-Shan Guo; Li Lu; Dian Li; Jun Liang; Zhong-Hui Huang; Yan-Mei Zhou; Wen-Juan Zhang; Shushan Du (Natural Product Research, 2021)

Overexpression of CcNAC1 gene promotes early flowering and enhances drought tolerance of jute (Corchorus capsularis L.) - Gaoyang Zhang; Siqi Huang; Chao Zhang; Defang Li; Yingbao Wu; Jielou Deng; Shilian Shan; Jianmin Qi (Protoplasma, 2021)

Assisted selection of eating quality progeny of indica (O. sativa L. ssp. indica) and japonica (O. sativa L. ssp. japonica) hybrids using rice starch properties - Ting Mao; Zhan Zhang; Shan Jun Ni; Yi Zhou Zhao; Xin Li; Li Li Zhang; Yan Liu; Cheng Shun Zhong; He Huang; Shao Lin Wang; Xu Li (Genetic Resources and Crop Evolution, 2021)

Three new andrastin derivatives from the endophytic fungus Penicillium vulpinum - Yu-Yue Qin; Xi-Shan Huang; Xiao-Bo Liu; Tu-Xiang Mo; Zhao-Long Xu; Ben-Chao Li; Xiao-Ya Qin; Jun Li; Till F. Schӓberle; Rui-Yun Yang (Natural Product Research, 2020)

Valine acts as a nutritional signal in brain to activate TORC1 and attenuate postprandial ammonia-N excretion in Chinese perch (Siniperca chuatsi) - Jie Wang; Xu-Fang Liang; Shan He; Yan-Peng Zhang; Jiao Li; Kang Huang; Lin-Jie Shi; Ping Ren (Fish Physiology and Biochemistry, 2020)

Effects of Extracellular Matrix Softening on Vascular Smooth Muscle Cell Dysfunction - Yihui Shao; Guoqi Li; Shan Huang; Zhenfeng Li; Bokang Qiao; Duanduan Chen; Yulin Li; Huirong Liu; Jie Du; Ping Li (Cardiovascular Toxicology, 2020)

Isopimarane-type diterpenoids from Croton laevigatus - Man-Yu Li; Zheng-Zhi Han; Li-Fang Liu; Xiao-Zhen Wu; Wen-Jun Huang; Kai Wang; Fan Yang; Cheng-Shan Yuan (Natural Product Research, 2020)

Metabolites from symbiotic bacteria of entomopathogenic nematodes have antimicrobial effects against Pythium myriotylum - Shaojie Shan; Haikun Ma; Yang Li; Cuiqing Huang; Xinghui Gu; Zhensheng Jiang; Bingjiao Sun; Chaoying Chen; Xianqin Wei; Guangshuang Shen; David Shapiro-Ilan; Weibin Ruan (European Journal of Plant Pathology, 2020)

Whole-Brain Monosynaptic Inputs to Hypoglossal Motor Neurons in Mice - Han Guo; Xiang-Shan Yuan; Ji-Chuan Zhou; Hui Chen; Shan-Qun Li; Wei-Min Qu; Zhi-Li Huang (Neuroscience Bulletin, 2020)
Hypoglossal motor neurons (HMNs) innervate tongue muscles and play key roles in a variety of physiological functions, including swallowing, mastication, suckling, vocalization, and respiration. Dysfunction of HMNs is associated with several diseases, such as obstructive sleep apnea (OSA) and sudden infant death syndrome. OSA is a serious breathing disorder associated with the activity of HMNs during different sleep–wake states. Identifying the neural mechanisms by which the state-dependent activities of HMNs are controlled may be helpful in providing a theoretical basis for effective therapy for OSA. However, the presynaptic partners governing the activity of HMNs remain to be elucidated. In the present study, we used a cell-type-specific retrograde tracing system based on a modified rabies virus along with a Cre/loxP gene-expression strategy to map the whole-brain monosynaptic inputs to HMNs in mice. We identified 53 nuclei targeting HMNs from six brain regions: the amygdala, hypothalamus, midbrain, pons, medulla, and cerebellum. We discovered that GABAergic neurons in the central amygdaloid nucleus, as well as calretinin neurons in the parasubthalamic nucleus, sent monosynaptic projections to HMNs. In addition, HMNs received direct inputs from several regions associated with respiration, such as the pre-Botzinger complex, parabrachial nucleus, nucleus of the solitary tract, and hypothalamus. Some regions engaged in sleep–wake regulation (the parafacial zone, parabrachial nucleus, ventral medulla, sublaterodorsal tegmental nucleus, dorsal raphe nucleus, periaqueductal gray, and hypothalamus) also provided primary inputs to HMNs. These results contribute to further elucidating the neural circuits underlying disorders caused by the dysfunction of HMNs.

Screening of Polymorphic SSR Molecular Markers Between Resistant and Susceptible Parents for Localization of Brown Rust Resistance Gene - Hongli Shan; Wenfeng Li; Yingkun Huang; Xiaoyan Wang; Rongyue Zhang; Jie Li; Zhiming Luo; Jiong Yin; Xiaoyan Cang (Sugar Tech, 2020)

Interaction between CA repeat microsatellites and HIF1α regulated the transcriptional activity of porcine IGF1 promoter - Hongwei Geng; Linlin Hao; Yunyun Cheng; Chunli Wang; Shan Huang; Wenzhen Wei; Rui Yang; Haoyang Li; Songcai Liu; Hao Yu; Huayi Lu (Journal of Applied Genetics, 2020)

Contribution of skeletal muscular glycine to rapid antidepressant effects of ketamine in an inflammation-induced mouse model of depression - Niannian Huang; Yue Wang; Gaofeng Zhan; Fan Yu; Shan Li; Dongyu Hua; Riyue Jiang; Shiyong Li; Yeshun Wu; Ling Yang; Bin Zhu; Fei Hua; et al. (Psychopharmacology, 2019)

Identification and Phylogenetic Analysis of Xanthomonas albilineans (Ashby) Dowson Based on Multiple Gene Sequences in Yunnan Province, China - Rong-Yue Zhang; Xiao-Yan Wang; Hong-Li Shan; Jie Li; Wen-Feng Li; Xiao-Yan Cang; Zhi-Ming Luo; Jiong Yin; Ying-Kun Huang (Sugar Tech, 2019)

Molecular Identification of Sugarcane White Leaf in Puer, Yunnan Province, China - Rong-Yue Zhang; Wen-Feng Li; Ying-Kun Huang; Xiao-Yan Wang; Hong-Li Shan; Jie Li; Xiao-Yan Cang; Zhi-Ming Luo; Jiong Yin (Sugar Tech, 2019)

Developing genetically segregating populations for localization of novel sugarcane brown rust resistance genes - Xiao-Yan Wang; Wen-Feng Li; Ying-Kun Huang; Hong-Li Shan; Rong-Yue Zhang; Jie Li; Xiao-Yan Cang; Zhi-Ming Luo; Jiong Yin (Euphytica, 2019)

Directed evolution of α-amylase from Bacillus licheniformis to enhance its acid-stable performance - Lin Huang; Mengying Shan; Jieying Ma; Yanzhen Li; Zehua Xu; Shulin Shao; Xingji Wang; Kefen Wang; Dongguang Xiao; Fuping Lu; Yihan Liu (Biologia, 2019)

Shaking table test and numerical simulation of an isolated cylindrical latticed shell under multiple-support excitations - Xue Suduo; Shan Mingyue; Li Xiongyan; Liang Shuanzhu; Huang Fuyun; Liu Yi (Earthquake Engineering and Engineering Vibration, 2019)

How much of Typhoon Morakot's extreme rainfall is attributable to anthropogenic climate change? - Chung‐Chieh Wang; Li‐Shan Tseng; Chien‐Chang Huang; Shih‐How Lo; Cheng‐Ta Chen; Pi‐Yu Chuang; Nan‐Chou Su; K. Tsuboki (International Journal of Climatology, 2019)
Typhoon Morakot (2009), which made landfall in Taiwan during August 7–9, 2009, produced the highest rainfall and became the deadliest typhoon ever recorded in Taiwan since 1958. To assess the role of anthropogenic climate change in the typhoon‐related torrent, we compare the water budget between a pair of cloud‐resolving sensitivity experiments. The pair consists of a control simulation that reproduces Typhoon Morakot (2009) in current climate and a sensitivity simulation in which the same storm is placed in a slightly different climate background where the late 20th century anthropogenic climate change signal is removed. The anthropogenic signal is estimated with the CMIP5 experiments of 18 models for the period of 1985–2005, during which the global warming trend is discernible. In climate states that differ merely by a 20‐year mean anthropogenic change, Morakot (2009) yields 3.4–3.6% more total rainfall in the control experiment than its sensitivity counterpart within a radius of 300–500 km from the storm centre. Water budget analysis indicates that the increase in typhoon rainfall is mainly resulted from the enhanced convergence of vapour flux. The enhancement is, in turn, contributed by the increased tropospheric moisture due to global warming and, to a lesser extent, by a more active secondary circulation in the storm that is associated with the anthropogenic climate change.

Identification and Evaluation of Resistance to Sugarcane Streak Mosaic Virus (SCSMV) and Sorghum Mosaic Virus (SrMV) in Excellent Sugarcane Innovation Germplasms in China - Wen-Feng Li; Hong-Li Shan; Xiao-Yan Cang; Xin Lu; Rong-Yue Zhang; Xiao-Yan Wang; Jiong Yin; Zhi-Ming Luo; Ying-Kun Huang (Sugar Tech, 2019)

Field Resistance of Different Sugarcane Varieties to Sugarcane Thrips (Fulmekiola serratus) in China - Zhi-Ming Luo; Xiao-Yan Wang; Ying-Kun Huang; Rong-Yue Zhang; Wen-Feng Li; Hong-Li Shan; Xiao-Yan Cang; Jie Li; Jiong Yin (Sugar Tech, 2019)

A miR-511-binding site SNP in the 3′UTR of IGF-1 gene is associated with proliferation and apoptosis of PK-15 cells - Wenzhen Wei; Gang Wang; Yunyun Cheng; Rui Yang; Jie Song; Shan Huang; Haoyang Li; Hongwei Geng; Hao Yu; Songcai Liu; Linlin Hao (In Vitro Cellular & Developmental Biology - Animal, 2019)

Selection of reference genes for real-time RT-PCR normalization in brown alga Undaria pinnatifida - Jing Li; Haishu Huang; Tifeng Shan; Shaojun Pang (Journal of Applied Phycology, 2019)

Limited potential of harvest index improvement to reduce methane emissions from rice paddies - Yu Jiang; Haoyu Qian; Ling Wang; Jinfei Feng; Shan Huang; Bruce A. Hungate; Chris van Kessel; William R. Horwath; Xingyue Zhang; Xiaobo Qin; Yue Li; Xiaomin Feng; et al. (Global Change Biology, 2019)
Rice is a staple food for nearly half of the world's population, but rice paddies constitute a major source of anthropogenic CH 4 emissions. Root exudates from growing rice plants are an important substrate for methane‐producing microorganisms. Therefore, breeding efforts optimizing rice plant photosynthate allocation to grains, i.e., increasing harvest index (HI), are widely expected to reduce CH 4 emissions with higher yield. Here we show, by combining a series of experiments, meta‐analyses and an expert survey, that the potential of CH 4 mitigation from rice paddies through HI improvement is in fact small. Whereas HI improvement reduced CH 4 emissions under continuously flooded (CF) irrigation, it did not affect CH 4 emissions in systems with intermittent irrigation (II). We estimate that future plant breeding efforts aimed at HI improvement to the theoretical maximum value will reduce CH 4 emissions in CF systems by 4.4%. However, CF systems currently make up only a small fraction of the total rice growing area (i.e., 27% of the Chinese rice paddy area). Thus, to achieve substantial CH 4 mitigation from rice agriculture, alternative plant breeding strategies may be needed, along with alternative management.

RETRACTED ARTICLE: Fluoxetine is Neuroprotective in Early Brain Injury via its Anti-inflammatory and Anti-apoptotic Effects in a Rat Experimental Subarachnoid Hemorrhage Model - Hui-Min Hu; Bin Li; Xiao-Dong Wang; Yun-Shan Guo; Hua Hui; Hai-Ping Zhang; Biao Wang; Da-Geng Huang; Ding-Jun Hao (Neuroscience Bulletin, 2018)

PGC-1α–FNDC5–BDNF signaling pathway in skeletal muscle confers resilience to stress in mice subjected to chronic social defeat - Gaofeng Zhan; Niannian Huang; Shan Li; Dongyu Hua; Jie Zhang; Xi Fang; Ning Yang; Ailin Luo; Chun Yang (Psychopharmacology, 2018)

An Automatic Method for Generating an Unbiased Intensity Normalizing Factor in Positron Emission Tomography Image Analysis After Stroke - Binbin Nie; Shengxiang Liang; Xiaofeng Jiang; Shaofeng Duan; Qi Huang; Tianhao Zhang; Panlong Li; Hua Liu; Baoci Shan (Neuroscience Bulletin, 2018)

High-resolution melting-based TILLING of γ ray-induced mutations in rice - Shan Li; Song-mei Liu; Hao-wei Fu; Jian-zhong Huang; Qing-yao Shu (Journal of Zhejiang University-SCIENCE B, 2018)

Particulate and gaseous pollutants in a petrochemical industrialized valley city, Western China during 2013–2016 - Xi Zhou; Tingjun Zhang; Zhongqin Li; Yan Tao; Feiteng Wang; Xin Zhang; Chunhai Xu; Shan Ma; Ju Huang (Environmental Science and Pollution Research, 2018)

Analysis of nonlinear associations between prenatal methylmercury exposure from fish consumption and neurodevelopmental outcomes in the Seychelles Main Cohort at 17 years - Li-Shan Huang; Deborah A. Cory-Slechta; Christopher Cox; Sally W. Thurston; Conrad F. Shamlaye; Gene E. Watson; Edwin van Wijngaarden; Grazyna Zareba; J. J. Strain; Gary J. Myers; Philip W. Davidson (Stochastic Environmental Research and Risk Assessment, 2018)

Epirubicin induces apoptosis in osteoblasts through death-receptor and mitochondrial pathways - Tzu-Ching Huang; Pu-Rong Chiu; Wen-Tsan Chang; Bau-Shan Hsieh; Yu-Ci Huang; Hsiao-Ling Cheng; Li-Wen Huang; Yu-Chen Hu; Kee-Lung Chang (Apoptosis, 2018)

Effects of genetic variants of the bovine WNT8A gene on nine important growth traits in beef cattle - Yong-Zhen Huang; Yong Zou; Qing Lin; Hua He; Li Zheng; Zi-Jing Zhang; Yong-Long Dang; Chu-Zhao Lei; Xian-Yong Lan; Xing-Shan Qi; Hong Chen (Journal of Genetics, 2017)

Three-dimensional arbitrarily anisotropic modeling for time-domain airborne electromagnetic surveys - Wei Huang; Fang Ben; Chang-Chun Yin; Qing-Min Meng; Wen-Jie Li; Gui-Xiang Liao; Shan Wu; Yong-Zai Xi (Applied Geophysics, 2017)

Molecular detection and phylogenetic analysis of viruses causing mosaic symptoms in new sugarcane varieties in China - Xiao-Yan Wang; Wen-Feng Li; Ying-Kun Huang; Rong-Yue Zhang; Hong-Li Shan; Jiong Yin; Zhi-Ming Luo (European Journal of Plant Pathology, 2017)

Two new biphenyls from the stems of Garcinia tetralata - Bing-Kun Ji; Xue-Mei Gao; Di Cui; Shan-Shan Wang; Wen-Zhong Huang; Yin-Ke Li; Shuang-Xi Mei; Zhi Yang; Gan-Peng Li; Meng-Yuan Jiang; Yong-Hui He; Zhi-Yong Jiang; et al. (Natural Product Research, 2017)

Molecular Detection of Bru1 Gene and Identification of Brown Rust Resistance in Chinese Sugarcane Germplasm - Wen-Feng Li; Xiao-Yan Wang; Ying-Kun Huang; Rong-Yue Zhang; Hong-Li Shan; Jiong Yin; Zhi-Ming Luo (Sugar Tech, 2017)

Properties and evolution of dissolved organic matter during co-composting of dairy manure and Chinese herbal residues - Qunliang Li; Yanyu Lu; Xiaobo Guo; Guangchun Shan; Junhao Huang (Environmental Science and Pollution Research, 2017)

Abnormal O-GlcNAcylation of Pax3 Occurring from Hyperglycemia-Induced Neural Tube Defects Is Ameliorated by Carnosine But Not Folic Acid in Chicken Embryos - Rui-Rong Tan; Yi-Fang Li; Shi-Jie Zhang; Wen-Shan Huang; Bun Tsoi; Dan Hu; Xin Wan; Xuesong Yang; Qi Wang; Hiroshi Kurihara; Rong-Rong He (Molecular Neurobiology, 2017)

A comparative study of strontium-substituted hydroxyapatite coating on implant’s osseointegration for osteopenic rats - Zhou-Shan Tao; Bing-Li Bai; Xing-Wen He; Wei Liu; Hang Li; Qiang Zhou; Tao Sun; Zheng-Liang Huang; Kai-kai Tu; Yang-Xun Lv; Wei Cui; Lei Yang (Medical & Biological Engineering & Computing, 2016)

Frequency and type of inheritable mutations induced by γ rays in rice as revealed by whole genome sequencing - Shan Li; Yun-chao Zheng; Hai-rui Cui; Hao-wei Fu; Qing-yao Shu; Jian-zhong Huang (Journal of Zhejiang University-SCIENCE B, 2016)

RETRACTED ARTICLE: Overexpression of miR-429 impairs intestinal barrier function in diabetic mice by down-regulating occludin expression - Tao Yu; Xi-Ji Lu; Jie-Yao Li; Ti-Dong Shan; Can-Ze Huang; Hui Ouyang; Hong-Sheng Yang; Ji-Hao Xu; Wa Zhong; Zhong-Sheng Xia; Qi-Kui Chen (Cell and Tissue Research, 2016)

A new flavone C -glycoside and a new bibenzyl from Bulbophyllum retusiusculum - Ming-Hui Yang; Yun-Shan Fang; Le Cai; Ying Li; Jian-Wei Dong; Tian-Peng Yin; Cai-Li Huang; Zhong-Tao Ding (Natural Product Research, 2016)

A new cytotoxic biflavonoid from the rhizome of Wikstroemia indica - Meng Shao; Xiao-Jun Huang; Jun-Shan Liu; Wei-Li Han; Hong-Bing Cai; Qing-Fa Tang; Qin Fan (Natural Product Research, 2016)

Selenium Deficiency Affects the mRNA Expression of Inflammatory Factors and Selenoprotein Genes in the Kidneys of Broiler Chicks - Jiu-li Zhang; Bo Xu; Xiao-dan Huang; Yu-hong Gao; Yu Chen; An-shan Shan (Biological Trace Element Research, 2016)

RETRACTED ARTICLE: MEK/ERK pathway activation by insulin receptor isoform alteration is associated with the abnormal proliferation and differentiation of intestinal epithelial cells in diabetic mice - Hui Ouyang; Hong-Sheng Yang; Tao Yu; Ti-Dong Shan; Jie-Yao Li; Can-Ze Huang; Wa Zhong; Zhong-Sheng Xia; Qi-Kui Chen (Molecular and Cellular Biochemistry, 2016)

Cloning and characterization of the geranylgeranyl diphosphate synthase (GGPS) responsible for carotenoid biosynthesis in Pyropia umbilicalis - Li-En Yang; Xing-Qi Huang; Qin-Qin Lu; Jian-Yi Zhu; Shan Lu (Journal of Applied Phycology, 2016)

Different Responses of an Invasive Clonal Plant Wedelia trilobata and its Native Congener to Gibberellin: Implications for Biological Invasion - Zhi-Cong Dai; Wei Fu; Shan-Shan Qi; De-Li Zhai; Si-Chong Chen; Ling-Yun Wan; Ping Huang; Dao-Lin Du (Journal of Chemical Ecology, 2016)

Effects of sialidase NEU1 siRNA on proliferation, apoptosis, and invasion in human ovarian cancer - Li-rong Ren; Li-ping Zhang; Shu-ying Huang; Yuan-fang Zhu; Wen-juan Li; Shan-yu Fang; Li Shen; Yan-ling Gao (Molecular and Cellular Biochemistry, 2016)

NK cell-based cancer immunotherapy: from basic biology to clinical application - Yang Li; Jie Yin; Ting Li; Shan Huang; Han Yan; JianMei Leavenworth; Xi Wang (Science China Life Sciences, 2015)

Subchronic effects of cadmium on the gonads, expressions of steroid hormones and sex-related genes in tilapia Oreochromis niloticus - Yongju Luo; Dan Shan; Huan Zhong; Yi Zhou; Wenzhi Chen; Jinling Cao; Zhongbao Guo; Jun Xiao; Fulin He; Yifan Huang; Jian Li; Heming Huang; et al. (Ecotoxicology, 2015)

Sinomonas halotolerans sp. nov., an actinobacterium isolated from a soil sample - Qian-Qian Guo; Hong Ming; Xiao-Lin Meng; Jian-Rong Huang; Yan-Yan Duan; Shan-Hui Li; Shuai Li; Jian-Xin Zhang; Wen-Jun Li; Guo-Xing Nie (Antonie van Leeuwenhoek, 2015)

Leaf and root glucosinolate profiles of Chinese cabbage (Brassica rapa ssp. pekinensis) as a systemic response to methyl jasmonate and salicylic acid elicitation - Yun-xiang Zang; Jia-li Ge; Ling-hui Huang; Fei Gao; Xi-shan Lv; Wei-wei Zheng; Seung-beom Hong; Zhu-jun Zhu (Journal of Zhejiang University-SCIENCE B, 2015)

Planococcus dechangensis sp. nov., a moderately halophilic bacterium isolated from saline and alkaline soils in Dechang Township, Zhaodong City, China - Kaibiao Wang; Lei Zhang; Jianying Li; Yuanyuan Pan; Lin Meng; Tong Xu; Cheng Zhang; Henan Liu; Shan Hong; Haipeng Huang; Juquan Jiang (Antonie van Leeuwenhoek, 2015)

Identification of Sugarcane White Leaf Phytoplasma in Fields and Quaratine Sugarcane Samples in Yunnan Province, China - Xiao-Yan Wang; Wen-Feng Li; Ying-Kun Huang; Rong-Yue Zhang; Hong-Li Shan; Zhi-Ming Luo; Jiong Yin; Ke Shen (Sugar Tech, 2015)

Effects of rice straw ash amendment on Cd solubility and distribution in a contaminated paddy soil under submergence - Sheng-Huie Hsu; Shan-Li Wang; Jang-Hung Huang; Shiuh-Tsuen Huang; Ming K. Wang (Paddy and Water Environment, 2015)

Local adaptation and phenotypic plasticity both occurred in Wedelia trilobata invasion across a tropical island - Chun-Can Si; Zhi-Cong Dai; Ying Lin; Shan-Shan Qi; Ping Huang; Shi-Li Miao; Dao-Lin Du (Biological Invasions, 2014)

Biodegradation of 1,4-Dioxane by a Novel Strain and Its Biodegradation Pathway - Huanlin Huang; Dongsheng Shen; Na Li; Dan Shan; Jiali Shentu; YuYang Zhou (Water, Air, & Soil Pollution, 2014)

Coumarin-containing aminophosphonates bridged with chiral side chain: synthesis and influence of chirality on cytotoxicity and DNA binding - Ya-Jun Li; Man-Yi Ye; Ri-Zhen Huang; Gui-Yang Yao; Ying-Ming Pan; Zhi-Xin Liao; Heng-Shan Wang (Medicinal Chemistry Research, 2014)

Tumour necrosis factor alpha (TNF-α) genetic polymorphisms and the risk of autoimmune liver disease: a meta-analysis - SHAN LI; XIAMEI HUANG; HUIZHI ZHONG; ZHIPING CHEN; QILIU PENG; YAN DENG; XUE QIN (Journal of Genetics, 2013)

A novel acridone akaloid from Atalantia buxifolia - Feng Shan; Yong-Qin Yin; Feng Huang; Yong-Chang Huang; Li-Bing Guo; Yu-Fei Wu (Natural Product Research, 2013)

Alantolactone induces apoptosis in chronic myelogenous leukemia sensitive or resistant to imatinib through NF-κB inhibition and Bcr/Abl protein deletion - Wei Wei; He Huang; Shan Zhao; Wei Liu; Chuan-Xu Liu; Li Chen; Jun-Min Li; Ying-Li Wu; Hua Yan (Apoptosis, 2013)

A novel steroidal alkaloid from Fritillaria shuchengensis - Shuai Huang; Xian-li Zhou; Juan Wen; Cui-juan Wang; Hong-yan Wang; Lian-hai Shan; Jie Weng (Journal of Natural Medicines, 2013)

Effect of sand-stabilizing shrubs on soil respiration in a temperate desert - Zhi-Shan Zhang; Xin-Rong Li; Robert S. Nowak; Pan Wu; Yan-Hong Gao; Yang Zhao; Lei Huang; Yi-Gang Hu; Rong-Liang Jia (Plant and Soil, 2013)

Composition and Distribution of Elements and Ultrastructural Topography of a Human Cardiac Calculus - Ching-Li Cheng; Hsiao-Huang Chang; Pei-Jung Huang; Yu-Ting Chu; Shan-Yang Lin (Biological Trace Element Research, 2013)

Erratum to: Altered regional homogeneity in Posttraumatic Stress Disorder: a resting state functional magnetic resonance imaging study - Yan Yin; Changfeng Jin; Lisa T. Eyler; Hua Jin; Xiaolei Hu; Lian Duan; Huirong Zheng; Bo Feng; Xuanyin Huang; Baoci Shan; Qiyong Gong; Lingjiang Li (Neuroscience Bulletin, 2013)

Wnt/β-catenin signaling induces the aging of mesenchymal stem cells through promoting the ROS production - Da-yong Zhang; Yu Pan; Chong Zhang; Bing-xi Yan; Shan-shan Yu; Dong-ling Wu; Meng-meng Shi; Kai Shi; Xin-xiao Cai; Shuang-shuang Zhou; Jun-bo Wang; Jian-ping Pan; et al. (Molecular and Cellular Biochemistry, 2013)

Dynamics of cadmium concentration in contaminated rice paddy soils with submerging time - Jang-Hung Huang; Shan-Li Wang; Jhin-Hao Lin; Yue-Ming Chen; Ming-Kuang Wang (Paddy and Water Environment, 2013)

Altered regional homogeneity in post-traumatic stress disorder: a restingstate functional magnetic resonance imaging study - Yan Yin; Changfeng Jin; Lisa T. Eyler; Hua Jin; Xiaolei Hu; Lian Duan; Huirong Zheng; Bo Feng; Xuanyin Huang; Baoci Shan; Qiyong Gong; Lingjiang Li (Neuroscience Bulletin, 2012)

Soil oxidases recovered faster than hydrolases in a 50-year chronosequence of desert revegetation - Zhi-Shan Zhang; Xue-Jun Dong; Yu-Bin Liu; Xin-Rong Li; Rong-Liang Jia; Yi-Gang Hu; Ming-Zhu He; Lei Huang (Plant and Soil, 2012)

Molecular epidemiological study of hepatitis B virus in blood donors from five Chinese blood centers - Yu Liu; Jingxing Wang; Yi Huang; Tonghan Yang; Xiaoming Guo; Julin Li; Guoxin Wen; Zhongqiao Yun; Peibin Zeng; Miao He; Min Xu; Gui Liu; et al. (Archives of Virology, 2012)

Erratum to: Biomass production and relative competitiveness of a C3 legume and a C4 grass co-dominant in the semiarid Loess Plateau of China - Bingcheng Xu; Weizhou Xu; Jin Huang; Lun Shan; Fengmin Li (Plant and Soil, 2012)

Analysis of Na+/Ca2+ exchanger (NCX) function and current in murine cardiac myocytes during heart failure - Lin Xu; Jing Chen; Xu-Yong Li; Shan Ren; Cong-Xin Huang; Gang Wu; Xiao-Yan Li; Xue-Jun Jiang (Molecular Biology Reports, 2012)

Polycyclic aromatic hydrocarbons in household dust near diesel transport routes - Chung-Yih Kuo; Heng-Chun Chen; Fang-Ching Cheng; Li-Ru Huang; Po-Shan Chien; Jing-Ya Wang (Environmental Geochemistry and Health, 2012)

Gambogenic acid-induced time- and dose-dependent growth inhibition and apoptosis involving Akt pathway inactivation in U251 glioblastoma cells - Hong-Bo Chen; Lan-Zhen Zhou; Lin Mei; Xiao-Jun Shi; Xiao-Shan Wang; Qing-Lin Li; Laiqiang Huang (Journal of Natural Medicines, 2012)

Biomass production and relative competitiveness of a C3 legume and a C4 grass co-dominant in the semiarid Loess Plateau of China - Bingcheng Xu; Weizhou Xu; Jin Huang; Lun Shan; Fengmin Li (Plant and Soil, 2011)

Cellular Toxicity of TiO2 Nanoparticles in Anatase and Rutile Crystal Phase - Chan Jin; Ying Tang; F. Guang Yang; X. Lin Li; Shan Xu; X. Yan Fan; Y. Ying Huang; Y. Ji Yang (Biological Trace Element Research, 2011)

Characterization of Exserohilum rostratum, a new causal agent of banana leaf spot disease in China - Shan-Hai Lin; Si-Liang Huang; Qi-Qin Li; Chun-Jin Hu; Gang Fu; Li-Ping Qin; Yue-Feng Ma; Ling Xie; Zhen-Lu Cen; Wei-Hong Yan (Australasian Plant Pathology, 2011)

β-Actin is a downstream effector of the PI3K/AKT signaling pathway in myeloma cells - Yen-Peng Ho; Chi-Wei Kuo; Yuan-Tong Hsu; Yu-Shan Huang; Li-Ping Yew; Wei-Feng Huang; Kuo-Chih Lin; Jung-Hsin Hsu (Molecular and Cellular Biochemistry, 2011)

Isolation of new esters from the stems of Cinnamomum reticulatum Hay - Iung-Jr Lin; Wen-Li Lo; Yi-Chen Chia; Lee-Yu Huang; Thau-Ming Cham; Wan-Shan Tseng; Yu-Ting Yeh; Hung-Chun Yeh; Yau-Der Wang; Chung-Yi Chen (Natural Product Research, 2010)

Isolation and characterization of 14 dinucleotide microsatellite loci in the endangered herb Saruma henryi Oliv. (Aristolochiaceae) - Shan-Shan Dong; Xuan Huang; Zeng-Qiang Qian; Tian-Hua Zhou; Shan Li; Gui-Fang Zhao (Conservation Genetics Resources, 2009)

An efficient method to enhance gene silencing by using precursor microRNA designed small hairpin RNAs - Zhixin Shan; Qiuxiong Lin; Chunyu Deng; Xiaohong Li; Wei Huang; Honghong Tan; Yongheng Fu; Min Yang; Xi-Yong Yu (Molecular Biology Reports, 2009)

Minocycline attenuates cognitive impairment and restrains oxidative stress in the hippocampus of rats with chronic cerebral hypoperfusion - Zhi-You Cai; Yong Yan; Shan-Quan Sun; Jun Zhang; Liang-Guo HUANG; Ning Yan; Fang Wu; Jie-Ying Li (Neuroscience Bulletin, 2008)

Adenovirus-mediated PDCD5 gene transfer sensitizes K562 cells to apoptosis induced by idarubicin in vitro and in vivo - Guo-Rui Ruan; Hong-Shan Zhao; Yan Chang; Jin-Lan Li; Ya-Zhen Qin; Yan-Rong Liu; Shan-Shan Chen; Xiao-Jun Huang (Apoptosis, 2008)

Human tau protein forms complex with PrP and some GSS- and fCJD-related PrP mutants possess stronger binding activities with tau in vitro - Xiao-Fan Wang; Chen-Fang Dong; Jin Zhang; Yan-Zhen Wan; Feng Li; Yin-Xia Huang; Lu Han; Bing Shan; Chen Gao; Jun Han; Xiao-Ping Dong (Molecular and Cellular Biochemistry, 2008)

A rice phenomics study—phenotype scoring and seed propagation of a T-DNA insertion-induced rice mutant population - Chyr-Guan Chern; Ming-Jen Fan; Su-May Yu; Ai-Ling Hour; Po-Chang Lu; Yao-Cheng Lin; Fu-Jin Wei; Sheng-Chung Huang; Shu Chen; Ming-Hsing Lai; Ching-Shan Tseng; Hsing-Mu Yen; et al. (Plant Molecular Biology, 2007)

A rice gene activation/knockout mutant resource for high throughput functional genomics - Yue-Ie Hsing; Chyr-Guan Chern; Ming-Jen Fan; Po-Chang Lu; Ku-Ting Chen; Shuen-Fang Lo; Peng-Kai Sun; Shin-Lon Ho; Kuo-Wei Lee; Yi-Chieh Wang; Wen-Lii Huang; Swee-Suak Ko; et al. (Plant Molecular Biology, 2007)

Effect of apple production base on regional water cycle in Weibei upland of the Loess Plateau - Huang Ming-bin; He Fu-hong; Yang Xin-min; Li Yu-shan (Journal of Geographical Sciences, 2001)